Electrodes for alkaline iron batteries

JP2024504099A5Active Publication Date: 2024-12-20FORM ENERGY INC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2023542515
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-01-13
Filing Date
2022-01-12
Publication Date
2024-12-20
Estimated Expiration
2042-01-12

AI Technical Summary

Technical Problem

Existing iron electrode batteries face performance degradation due to unstable sulfide concentrations in the electrolyte, leading to issues such as low rate capacity, capacity loss, and high self-discharge rates, which are not effectively addressed by current technologies.

Method used

Incorporating crystalline cubic zinc sulfide and manganese sulfide additives into the iron electrode batteries, which maintain sulfide concentrations within a narrow range by controlling thermodynamic solubility and kinetic dissolution rates, thereby extending the battery's life and enhancing performance.

Benefits of technology

The use of crystalline cubic zinc sulfide and manganese sulfide additives stabilizes sulfide concentrations, improving cycle life, discharge rates, energy efficiency, and reducing self-discharge, thus enhancing the overall performance and longevity of iron electrode batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

Various embodiments may include a battery electrode comprising an iron electrode body comprising an iron active material and a zinc sulfide additive, the zinc sulfide additive comprising crystalline cubic zinc sulfide. Various embodiments may include a battery electrode comprising an iron electrode body comprising an iron active material and a manganese sulfide additive, the manganese sulfide additive comprising crystalline cubic manganese sulfide. Various embodiments may include an iron electrode battery comprising an iron electrode and a sulfide reservoir separated from the iron electrode, the sulfide reservoir comprising crystalline cubic zinc sulfide. Various embodiments may include an iron electrode battery comprising an iron electrode and a sulfide reservoir separated from the iron electrode, the sulfide reservoir comprising crystalline cubic manganese sulfide.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] This application claims the benefit of priority to U.S. Provisional Patent Application No. 63 / 136,746, entitled "Electrodes for Alkaline Iron Batteries," filed January 13, 2021, the contents of which are incorporated herein by reference in their entirety for all purposes. This application also relates to subject matter disclosed in International Publication No. WO 2019133702, published July 4, 2019 (hereinafter "Pham Publication '702"), the entirety of which is incorporated herein by reference for all purposes to the extent not inconsistent with the disclosure herein.

[0002] The present invention relates generally to battery electrodes, and more specifically to battery electrodes having iron active material. [Background technology]

[0003] Energy storage technologies are playing an increasingly important role in the power grid. At the most basic level, these energy storage assets provide smoothing to better match generation and demand in the grid. The services performed by energy storage devices benefit the power grid over multiple timescales, from milliseconds to days. Batteries range in size from the order of watts for backup power, to kilowatts for communication systems, to megawatts for large scale power grids.

[0004] This "Background" section is intended to introduce various aspects of the art that may be related to embodiments of the present invention. As such, the discussion above in this section is intended to provide a framework for better understanding the present invention, and should not be construed as admissions of prior art. Summary of the Invention

[0005] Various embodiments of systems and methods are provided herein for the manufacture and use of additives that have been found to be particularly useful in enhancing the performance of iron electrode batteries. The additives generally comprise substantially all zinc sulfide (also represented herein by the formula "ZnS") and / or manganese sulfide (also represented herein by the formula "MnS") in a particular crystalline form.

[0006] Various embodiments include a battery electrode comprising an iron electrode body comprising an iron active material and a zinc sulfide additive, the zinc sulfide additive comprising crystalline cubic zinc sulfide.

[0007] Various embodiments include a battery electrode comprising an iron electrode body comprising an iron active material and a manganese sulfide additive, the manganese sulfide additive comprising crystalline cubic manganese sulfide.

[0008] Various embodiments include an iron electrode battery comprising an iron electrode and a sulfide reservoir separated from the iron electrode, the sulfide reservoir comprising crystalline cubic zinc sulfide.

[0009] Various embodiments include an iron electrode battery comprising an iron electrode and a sulfide reservoir separated from the iron electrode, the sulfide reservoir comprising crystalline cubic manganese sulfide.

[0010] The novel features of the invention are set forth with particularity in the following claims. A better understanding of the features and advantages of the present disclosure will be obtained by reference to the following detailed description of illustrative embodiments, in which the principles of the present disclosure are utilized, and the accompanying drawings. [Brief description of the drawings]

[0011] [Figure 1A] FIG. 1 illustrates an example of an electrochemical cell, which may be an iron electrode battery, in accordance with aspects of various embodiments.

[0012] [Figure 1B]FIG. 1 illustrates an example of an electrochemical cell, which may be an iron electrode battery, in accordance with aspects of various embodiments.

[0013] [Figure 1C] FIG. 1 is a series of schematic diagrams showing the change in sulfide concentration during soak time for samples having various ratios of zinc sulfide solid and liquid electrolyte.

[0014] [Figure 2A] FIG. 1 is a schematic diagram of X-ray diffraction spectra showing two samples of iron electrodes containing a "non-structured" cubic zinc sulfide additive and a "crystalline" zinc sulfide additive.

[0015] [Figure 2B] FIG. 2B is a schematic diagram showing a zoom in on the XRD peak labeled 200 in FIG. 2A, illustrating the difference in full width at half maximum (FWHM) values ​​of the peak for the two samples.

[0016] [Diagram 3] FIG. 1 is a schematic showing the range of FWHM values ​​for selected peak positions of unstructured cubic ZnS and crystalline cubic ZnS samples.

[0017] [Figure 4] 1A-1D illustrate various exemplary systems in which one or more aspects of various embodiments may be used as part of a bulk energy storage system. [Diagram 5] 1A-1D illustrate various exemplary systems in which one or more aspects of various embodiments may be used as part of a bulk energy storage system. [Figure 6] 1A-1D illustrate various exemplary systems in which one or more aspects of various embodiments may be used as part of a bulk energy storage system. [Figure 7] 1A-1D illustrate various exemplary systems in which one or more aspects of various embodiments may be used as part of a bulk energy storage system. [Figure 8]1A-1D illustrate various exemplary systems in which one or more aspects of various embodiments may be used as part of a bulk energy storage system. [Figure 9] 1A-1D illustrate various exemplary systems in which one or more aspects of various embodiments may be used as part of a bulk energy storage system. [Figure 10] 1A-1D illustrate various exemplary systems in which one or more aspects of various embodiments may be used as part of a bulk energy storage system. [Figure 11] 1A-1D illustrate various exemplary systems in which one or more aspects of various embodiments may be used as part of a bulk energy storage system. [Figure 12] 1A-1D illustrate various exemplary systems in which one or more aspects of various embodiments may be used as part of a bulk energy storage system. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] Various embodiments will be described in detail with reference to the accompanying drawings. References to specific examples and implementations are for illustrative purposes only and are not intended to limit the scope of the invention or the claims. Wherever possible, the same reference numbers will be used throughout the drawings to refer to the same or similar parts. References to specific examples and implementations are for illustrative purposes only and are not intended to limit the scope of the claims. The following description of embodiments of the invention is not intended to limit the invention to such embodiments, but rather to enable one of ordinary skill in the art to make and use the invention. Unless otherwise noted, the accompanying drawings are not drawn to scale.

[0019] The following examples are provided to illustrate various embodiments of the present systems and methods of the present invention. Such examples are intended to be illustrative and may be prophetic, and should not be considered limiting or in any way limit the scope of the present invention.

[0020] It should be noted that it is not necessary to provide or express the theory underlying the novel and innovative process, material, performance, or other beneficial features and characteristics that are the subject of or associated with embodiments of the present invention. Nevertheless, various theories are provided herein to further advance the art in the field. The theories presented herein are not intended to limit, restrict, or narrow in any way the scope of protection afforded to the claimed invention unless expressly stated otherwise. Such theories may not be necessary to the utilization of the present invention or may not be practiced. Furthermore, it is understood that the present invention may be coupled with new and previously unknown theories to explain the function-characteristics of embodiments of the methods, articles, materials, devices, and systems of the present invention. Such subsequently developed theories shall not limit the scope of protection afforded to the present invention.

[0021] The various embodiments of the systems, facilities, techniques, methods, activities, and operations shown herein can be used in various other activities and fields in addition to those shown herein. In addition, such embodiments can be used, for example, with other facilities or activities that may be developed in the future and with existing facilities or activities that may be modified in part based on the teachings herein. Furthermore, the various embodiments and examples shown herein can be used with each other, in whole or in part, and in various different combinations. Thus, the configurations provided in the various embodiments herein can be used with each other. For example, elements of an embodiment having A, A', and B, and elements of an embodiment having A", C, and D can be used with each other in various combinations, for example, A, C, D, and A, A", C, D, etc., in accordance with the teachings herein. Thus, the scope of protection given to the present invention should not be limited to the specific embodiments, configurations, or arrangements shown in the specific embodiments, examples, or in the specific illustrated embodiments.

[0022] As used herein, unless otherwise stated, room temperature is 25° C. and standard temperature and pressure are 25° C. and 1 atmosphere. Unless expressly stated otherwise, all tests, test results, physical properties, and values ​​that are temperature dependent, pressure dependent, or both, are provided at standard ambient temperature and pressure.

[0023] Various embodiments of systems and methods are provided herein for the manufacture and use of additives that have been found to be particularly useful for enhancing the performance of iron electrode batteries. The additives generally include zinc sulfide (also represented herein by the formula "ZnS") and / or manganese sulfide (also represented herein by the formula "MnS"), substantially all of which are in a particular crystalline form. As described in more detail below, crystalline cubic ZnS has been found to produce dissolved sulfide concentrations in 6M KOH that are an order of magnitude lower than other crystalline forms of ZnS. This lower sulfide concentration allows electrolyte sulfide concentrations to be maintained within an ideal range for extended periods of time that has been shown to extend the life and enhance the performance of iron electrode batteries. Various examples and embodiments of iron electrode batteries containing ZnS, substantially all of which are in the form of crystalline cubic ZnS, are also described herein. Crystalline cubic MnS is contemplated herein to produce similar results.

[0024] Without wishing to be bound by theory, there may be consideration herein for reliance on or understanding of underlying principles with respect to the devices and methods disclosed herein, and the inventors recognize that regardless of the ultimate correctness of any mechanistic explanation or hypothesis, embodiments of the invention may still be effective and useful.

[0025] As used herein, the term "iron electrode" refers to a porous or nonporous, rigid or flexible, conductive structure containing iron active material that can participate in an electrochemical reaction in an electrochemical device such as a primary or secondary battery, electrolyzer, or other electrochemical cell. Iron electrodes can be manufactured by any available technique or combination of techniques, such as sintering, hot pressing, cold pressing, wet paste lamination, dry pressing, slurry coating, PTFE-based processes, roll bonding, tape casting (blade coating) pocket filling, or other suitable processes. In various embodiments, iron electrodes can also include materials such as additive materials, pore formers, binders, current collectors, supports, conductivity enhancing additives, and the like.

[0026] As used herein, the term "iron active material" refers to an iron-containing material capable of undergoing an oxidation reaction during discharge of an electrochemical cell and / or a reduction reaction during charging of an electrochemical cell. Specifically, iron active materials include metallic iron (Fe) and / or one or more iron hydroxides (e.g., Fe(OH) 2 , Fe(OH) 3 ), anhydrous and / or hydrated iron oxyhydroxides (e.g., FeOOH; e.g., FeO(OH) nH 2 O, where n is the number of water molecules in the hydrated iron hydroxide molecule), oxides, suboxides and mixed oxides of iron, e.g. FeO (wüstite), FeO 2 (iron dioxide), Fe 2 O 3 , Fe 3 O 4 (Magnetite), Fe 4 O 5 , Fe 5 O 6 , Fe 5 O 7 , Fe 25 O 32 , Fe 13 O 19 , other iron-containing compounds, any polymorph(s) thereof, and / or any combination thereof.

[0027] As used herein, the term "iron electrode battery" refers to a primary (disposable, discharge only) or secondary (rechargeable) battery that contains an iron active material that undergoes oxidation-reduction at the negative electrode of the battery. In some embodiments, an iron electrode battery may contain iron active material as the major component of the negative electrode (i.e., greater than 50% of the electrode active material is one or more iron active materials). Some examples of iron electrode batteries include nickel-iron batteries (NiOOH-Fe), manganese dioxide-iron batteries (MnO 2 -Fe), iron-air batteries (Fe-O2 batteries, which may include flow batteries or hybrid battery / fuel cell systems), flow batteries such as silver-iron batteries (Ag-Fe), all-iron flow batteries, or other batteries with electrodes that temporarily or permanently contain iron active material. The term "manganese dioxide" encompasses a number of manganese oxide phases known to function as battery cathodes, such as gamma, delta, birnessite, or other manganese oxide phases produced by chemical or electrolytic or other synthetic processes.

[0028] Embodiments of the present invention include devices, systems, and methods for long-term and ultra-long-term low-cost energy storage. As used herein, "long-term" and / or "ultra-long-term" may refer to energy storage periods of 8 hours or more, such as an 8-hour energy storage period, an energy storage period ranging from 8 hours to 20 hours, an energy storage period ranging from 20 hours to 24 hours, an energy storage period ranging from 24 hours to 1 week, an energy storage period ranging from 1 week to 1 year (e.g., from days to weeks to months). In other words, "long-term" and / or "ultra-long-term" energy storage cells refer to electrochemical cells that may be configured to store energy for days, weeks, or seasons. For example, an electrochemical cell may be configured to store energy generated by a solar cell during summer months when sunlight is abundant and solar power generation exceeds power grid needs, and discharge the stored energy during winter months when sunlight may be insufficient to meet power grid needs.

[0029] Other embodiments include backup power sources for telecommunications, data centers, electronic devices, traffic signals, medical facilities, or buildings. The duration of power delivery from the battery can range from minutes to hours. The energy storage and / or power delivery durations described herein are provided by way of example only and are not intended to be limiting.

[0030] FIG. 1A illustrates an example of an electrochemical cell, which may be an iron electrode battery, according to aspects of various embodiments. An electrochemical cell includes a negative electrode, a positive electrode, an electrolyte, and a separator disposed between the positive and negative electrodes (e.g., as shown in FIG. 1A). FIG. 1A illustrates an example of an electrochemical cell 100, such as a battery, including a negative electrode and an electrolyte 102 separated from a positive electrode and an electrolyte 103 by a separator 104. The separator 104 may optionally be supported by a polypropylene mesh 105 and a polyethylene or polypropylene frame 108 of the cell 100. Current collectors 107 may be attached to each of the negative electrode 102 and positive electrode 103 and supported by a polyethylene or polypropylene backing plate 106. In some embodiments, the temperature of the electrochemical cell 100 may be controlled, such as by insulation around the cell 100 and / or a heater 150. For example, the heater 150 may increase the temperature of the cell 100 and / or certain components of the cell, such as the electrolytes 102, 103. The configuration of electrochemical cell 100 in Figure 1A is merely an example of one electrochemical cell configuration according to various embodiments and is not intended to be limiting. Other configurations, such as electrochemical cells with different types of meshes and / or without polypropylene mesh 105, electrochemical cells with different types of frames and / or without polyethylene frame 108, electrochemical cells with different types of current collectors and / or without current collectors, electrochemical cells with reservoir structures (such as one or more of the various sulfide reservoirs discussed in Pham Publication '702), electrochemical cells with different types of backing plates and / or without polyethylene backing plate 106, electrochemical cells with different types of insulators and / or without insulators, electrochemical cells with different types of heaters and / or without heater 150, may be substituted for the example configuration of electrochemical cell 100 shown in Figure 1A, and other configurations are in accordance with various embodiments.

[0031] In some embodiments, multiple electrochemical cells 100 of Figure 1A may be electrically connected in series to form a stack. In certain other embodiments, multiple electrochemical cells 100 may be electrically connected in parallel. In certain other embodiments, multiple electrochemical cells 100 are connected in a mixed series-parallel electrical configuration to provide a preferred combination of supplied currents and voltages.

[0032] According to various embodiments, the negative electrode is comprised of an iron-containing material. The iron-containing material may be a pelletized, briquette, pressed, or sintered iron-bearing compound. Such iron-containing compounds may include one or more forms of iron ranging from highly reduced (more metallic) iron to highly oxidized (more ionic) iron. In various embodiments, the pellets may include various iron compounds, such as iron oxide, iron hydroxide, iron sulfide, iron carbide, or combinations thereof. In various embodiments, the negative electrode may be a sintered iron-containing material having various shapes. In some embodiments, atomized iron powder or sponge iron powder may be used as a feed material for forming the sintered iron electrode. In some embodiments, the green body may further include a binder, such as a polymer or an inorganic clay-like material. In various embodiments, the sintered iron-containing material pellets may be formed in a furnace, such as a continuous feed calcining furnace, a batch feed calcining furnace, a blast furnace, a rotary calcining furnace, or a rotary hearth. In various embodiments, the pellets may include a form of reduced and / or sintered iron-bearing precursor, known to those skilled in the art as direct reduced iron (DRI), and / or its by-product materials.

[0033] According to various embodiments, an electrochemical cell, such as cell 100 of FIG. 1A, comprises a negative electrode (also called an anode), a positive electrode (also called a cathode), and an electrolyte. The negative electrode may be a ferrous material. The electrolyte may be an aqueous solution. In certain embodiments, the electrolyte may be an alkaline solution (pH>10). In certain embodiments, the electrolyte may be a near-neutral solution (10>pH>4).

[0034] FIG. 1B illustrates an example of an electrochemical cell that may be an iron electrode battery according to aspects of various embodiments. FIG. 1B illustrates a secondary (rechargeable) battery system 10 including a positive electrode 12, a negative electrode 14, and a separator 16 in a battery container 18 filled with electrolyte 20 up to a level 22 that is at least the height of the tops 32, 34 of the electrodes 12, 14. The space above the electrolyte level 22 may be referred to as headspace 24. The positive electrode 12 may be electrically connected to the positive terminal 42 of the battery and may contain an active material that undergoes a reduction reaction during discharge and an oxidation reaction during charging. The negative electrode 14 may be electrically connected to the negative terminal 44 of the battery and may contain an active material that undergoes a reduction reaction during discharge and an oxidation reaction during charging of the battery 10. The electrochemical cell configuration of FIG. 1B is merely an example of one electrochemical cell configuration according to various embodiments and is not intended to be limiting.

[0035] The negative electrode 14 active material may include metals or metal oxides, such as iron, zinc, cadmium, or other metals, and / or oxides or hydroxides of these or other metals. In some embodiments, the iron negative electrode active material may include elemental iron and / or iron provided as an iron-containing material (e.g., an iron-containing alloy, or an iron-containing compound, such as iron oxide, mixed iron oxide, iron hydroxide, iron sulfate, iron carbide, iron sulfide, or any combination thereof). In some embodiments, the iron negative electrode active material may include refined or smelted iron materials, such as carbonyl iron or electrolytic iron, or iron ores, such as magnetite, maghemite, iron carbonate, hematite, goethite, limonite, or other iron materials.

[0036] In some embodiments, the iron negative electrode may contain carbonyl iron or other iron active material (e.g., magnetite, hematite, or other iron oxides or hydroxides) and two or more soluble metal sulfide additives in an amount of about 0.01% (as a percentage of the weight of the carbonyl iron) to 10% or more by weight. For example, the iron negative electrode may contain an iron active material, an iron sulfide additive in an amount of about 0.01% to about 10% by weight of the iron active material, and a second sulfide compound in an amount of about 0.01% to about 10% by weight of the iron active material (e.g., bismuth sulfide, iron sulfide, iron disulfide, iron-copper sulfide, zinc sulfide, manganese sulfide, tin sulfide, copper sulfide, cadmium sulfide, suboxide of iron sulfide, silver sulfide, titanium disulfide, lead sulfide, molybdenum sulfide, nickel sulfide, antimony sulfide, dimethyl sulfide, carbon disulfide, etc.).

[0037] In various embodiments, the electrolyte 20 may be an aqueous or non-aqueous alkaline, neutral, or acidic solution. For example, the electrolyte solution may contain potassium hydroxide (KOH), sodium hydroxide (NaOH), lithium hydroxide (LiOH), or combinations thereof.

[0038] In some embodiments, the battery 10 may include a separator 16 configured to allow ion movement between the electrodes 12, 14 through the electrolyte. In some embodiments, the separator may be selected based on its ability to allow selective movement of desired molecules or materials while substantially limiting or preventing the movement of undesired molecules or materials. For example, some separator membranes are ion-selective, allowing the movement of anions (or cations) while substantially preventing the movement of cations (or anions). In other examples, the separator material may be selected based on its ability to permit or prevent the crossing of gas bubbles from one side (the side associated with one electrode) to the other side (the side associated with the opposing electrode).

[0039] In various embodiments, battery container 18 may be made of any suitable material and construction capable of containing the electrolyte, electrodes, and at least a minimal amount of gas pressure. For example, battery container 18 may be made of metal, plastic, composite materials, etc. In some embodiments, battery container 18 may be sealed to prevent escape of gases generated during operation of the battery.

[0040] In some embodiments, battery container 18 may include a pressure relief valve that allows gas to be released when gas pressure within battery container 18 exceeds a preset threshold.

[0041] The electrodes 12, 14 are shown substantially spaced apart, however, in some embodiments, the electrodes may be in close proximity to one another or even compressed against one another with a separator 16 between them. Additionally, while the figures may show one positive electrode 12 and one negative electrode 14, battery systems within the scope of the present disclosure may include two or more positive electrodes 12 and / or two or more negative electrodes 14.

[0042] 1B also illustrates several example locations that the sulfide reservoirs (e.g., 58, 56, and / or 62) may have within or relative to the battery container. The example sulfide reservoir locations illustrated in FIG. 1B are merely examples of configurations according to various embodiments and are not intended to be limiting. Sulfide reservoirs 58, 56, and / or 62 may be any type of reservoir structure, such as one or more of the various sulfide reservoirs discussed in the Pham '702 publication.

[0043] To further extend the working life of nickel-iron batteries that require minimal maintenance, a long-term reservoir of soluble sulfide may be provided within the battery. As used herein, the term "sulfide reservoir" may refer to a source of sulfide ions other than "additive sulfide" and "incorporated sulfide," either of which are located within and in electrical communication with the iron negative electrode. The "reservoir sulfide" may be located outside the iron electrode but in electrical communication with it, inside but electrically insulated or disconnected from it, or outside and electrically disconnected from it. Sulfide may generally be released from the sulfide reservoir into the electrolyte by chemical reaction, electrochemical reaction, phase change reaction, and / or controlled mechanical action (e.g., movement of a servo, piston, relay, or other electromechanical device), or a combination of these or other mechanisms.

[0044] In some embodiments, a closed-loop automatic control system may be configured to directly or indirectly detect a condition or event that indicates the need for sulfide addition to the electrolyte, and to supply or release an amount of sulfide source material from a sulfide reservoir to the electrolyte upon detection of the event or condition. For example, in some embodiments, a sulfide detector (e.g., a sulfide ion-selective electrode, an optical sulfide detector, etc.) may be connected to an automatic controller configured to periodically or continuously detect the sulfide concentration in the electrolyte with the sulfide detector. In response to detecting a sulfide concentration below a threshold, the control system may actuate an actuator device to supply the sulfide source material to the electrolyte. For example, the actuator may be a pump, syringe, or plunger configured to supply an amount of solid or liquid sulfide source material to the electrolyte, e.g., the amount may be the same or different each time.

[0045] In other embodiments, the automatic control system may be configured to detect one or more events that may indicate a need for sulfide in the electrodes. For example, the electronic controller may be configured to monitor the performance of the cell and, in response to detecting a low-sulfide event, activate the actuator to supply sulfide source material to the electrolyte. Examples of low-sulfide events include a decrease in coulombic efficiency beyond a change threshold, a decrease in discharge rate capacity beyond a quantity threshold, overcharging for an extended period of time (e.g., overcharging for a certain time or a predetermined amount in coulombs), a change in electrolyte conductivity beyond a quantity threshold, or other events.

[0046] In some embodiments, the low sulfide event may be "detected" chemically or electrochemically in such a way as to chemically or electrochemically trigger the automatic release of sulfide. In one embodiment, for example, the system is configured such that detection or characterization of a low sulfide event is used as a triggering event to cause the "automatic release" of sulfide, e.g., using an active or passive system or method for sulfide release.

[0047] In various embodiments, the actuator may be configured to release or provide a fixed amount of sulfide each time the actuator is triggered, or the actuator may be configured to release or provide an amount of sulfide proportional to a quantitative measurement of the trigger event.

[0048] In some embodiments, the sulfide reservoir may be configured to slowly release sulfide ions into the electrolyte at a location adjacent the negative electrode in the battery such that a significant portion of the released sulfide ions reach the iron electrode to replace consumed sulfide. In some embodiments, the sulfide source material of the sulfide reservoir is iron sulfide (e.g., FeS, FeS 2 , Fe 3 S 4 or other iron sulfide compounds or combinations thereof), zinc sulfide, manganese sulfide, lead sulfide, nickel sulfide, tin sulfide, bismuth sulfide, copper sulfide (CuS, Cu 2In some embodiments, the sulfide source material for the sulfide reservoir may include one or more soluble metal sulfides, including FeS, ... 1-x O x In some embodiments, preferred materials for the sulfide reservoir may include refractory metal sulfides, i.e., metal sulfides that release 10 mmoles or less of sulfide ions per liter of electrolyte at temperatures up to 70° C.

[0049] In some embodiments, the sulfide reservoir may be configured to slow the release rate of sulfide from the reservoir into the electrolyte. The release rate of sulfide from the sulfide reservoir may be a function of the rate of dissolution if the reservoir is a solid sulfide source that releases sulfide by dissolution, the rate of electrochemical reduction if the reservoir is configured to release sulfide ions by electrochemical reaction (e.g., by electrochemical reduction of a solid sulfide source in electrical communication with the negative electrode), the rate of injection or release of a liquid sulfide source, and / or a gaseous sulfur source (e.g., SO 2 or H 2 S) release and / or dissolution rate.

[0050] The rate of dissolution of a solid sulfide reservoir in an aqueous alkaline battery electrolyte can be a function of, among other things, the surface area of ​​the sulfide reservoir exposed to the electrolyte, the rate of dissolution of the sulfide source material, the diffusion rate and / or dissolution rate of the barrier surrounding the sulfide source material, the temperature of the electrolyte, the solubility limit (saturation limit) of the sulfide reservoir material, and the rate at which sulfide is removed from the electrolyte by absorption at the negative electrode or by irreversible conversion to sulfite or sulfate.

[0051] In some embodiments, the sulfide reservoir may be a "slow-releasing sulfide reservoir" in that it is configured to provide sulfide ions to the electrolyte at a rate slower than the natural dissolution rate of the same sulfide source material placed directly in the electrolyte. In other words, a "slow-releasing" sulfide reservoir may have a sulfide ion release rate that is lower than the natural dissolution rate of the sulfide source material contained in the reservoir. Some embodiments of a slow-releasing sulfide reservoir may include structures and materials selected to dissolve and / or otherwise release sulfide ions at a predictably slow rate under conditions expected to be experienced by a battery in operation. In some embodiments, the sulfide ion release rate may approximately match the rate of sulfide consumption (e.g., conversion to sulfate ions by oxygen or the positive electrode), such that the instantaneous sulfide concentration in the electrolyte at any given time or the average sulfide concentration over a period of time may be maintained within a desired range.

[0052] FIG. 1B illustrates several alternative locations where the sulfide reservoir may be located inside and outside the battery container 18, along with corresponding ion and / or gas passageways. For example, the sulfide reservoir may be located completely or partially in the headspace 24 above the electrolyte level 22. Another exemplary embodiment is represented by a sulfide reservoir 56 positioned such that a portion of the sulfide reservoir 56 extends below the electrolyte level 22. In some embodiments, the sulfide reservoir 56 is fixedly secured to the battery container 18 (or another structure) in a fixed position relative to the electrolyte level 22. In some embodiments, the sulfide reservoir 58 may be located completely below the electrolyte level. FIG. 1B illustrates the sulfide reservoir 58 submerged below the electrolyte level 22. FIG. 1B also illustrates a sulfide reservoir 62 located outside the battery container 18. The sulfide reservoir 62 may be connected to the battery by an electrolyte conduit 66 that extends between the sulfide reservoir 62 and the electrolyte 22 within the battery container 18 .

[0053] The presence of sulfide compounds in an iron electrode battery can affect a variety of performance indicators, including calendar life, cycle life, charge and / or discharge rate capacity; the ability of the electrode to be discharged at a relatively high rate; coulombic efficiency; and self-discharge rate. Sulfide is believed to participate in and / or facilitate intermediate reactions during charging and / or discharging of the iron electrode. Furthermore, sulfide involved in such reactions is believed to be primarily in the form of sulfide ions dissolved in the aqueous electrolyte (alkaline or acidic aqueous solution). A number of electrolyte-soluble sulfide compounds can be used as source materials for sulfide uptake by the iron electrode. Although various mechanisms have been proposed to explain exactly how sulfide benefits iron electrode batteries, the inventors have demonstrated a clear benefit that the persistent presence of sulfide has on the long-term performance of iron electrode batteries.

[0054] Sulfide can be irreversibly lost from the iron electrode and electrolyte by multiple mechanisms under a variety of conditions. Solid sulfide can be "lost" from the iron electrode by dissolution or electrochemical reduction, releasing sulfide into the bulk electrolyte. The dissolved sulfide ions can then be oxidized to sulfite or sulfate (or other sulfur compounds) upon encounter with dissolved oxygen at the positive electrode or in the electrolyte. It is believed that the oxidized sulfur species cannot be easily converted back to sulfide to participate in the iron electrode enhancing reactions.

[0055] The term "sulfide compound" refers to a chemical species that contains sulfide ion(s) or that can become sulfide ion(s) when dissolved in an electrolyte. The sulfide compound may refer to "incorporated sulfide" compounds, "additive sulfide" compounds, "sulfide source materials" in a "sulfide reservoir", or all of these, as these terms are defined in the Pham '702 publication, supra. The term "sulfide ion" refers to S 2- or S 2-The term "sulfide" refers to an ion containing sulfide ions. The sulfide ions may be present in a solid form as part of a solid compound (e.g., a solid ionic compound). The sulfide ions may be dissolved sulfide ions, such as sulfide ions dissolved in an electrolyte. The term "sulfide" may refer to sulfide ions or sulfide ion-containing compounds. In some embodiments, the term "sulfide" refers to a sulfide ion or ions. At least a portion of the additive sulfide in an iron electrode battery is in contact with the electrolyte.

[0056] The term "solubility limit" is generally understood to refer to the maximum amount of solute that can be dissolved in a solvent at a particular temperature and pressure. Solubility can be expressed as mass of solute per volume (g / L), mass of solute per mass of solvent (g / g), or moles of solute per volume (mol / L). A solution in which the maximum amount of solute possible at a given temperature has been dissolved (i.e., the solute concentration is equal to the solubility limit) is called "saturated." In general, when a solution is saturated and there is excess solute, the rate of dissolution of the solute is equal to the rate of crystallization (or precipitation) of the solid solute. A solution in which more solute has been dissolved than the solubility limit is called "supersaturated."

[0057] As used herein, the "concentration" of a dissolved ionic species is the amount of the ionic species per unit volume, and is typically expressed herein in moles of ion per liter (mol / L), also referred to as molarity, denoted by the symbol "M."

[0058] As used herein, the terms "crystalline phase" and "crystalline morphology" refer to the crystal structure of a crystallite, which is characterized by a unit cell or repeating structural pattern of the atoms of the crystallite. The term "crystallite" refers to a single crystalline volume of a solid material having the same chemical composition and crystal structure throughout its volume. A crystallite can be a grain within a material, such as a thin film or a bulk material. A particle can be, for example, a single crystallite or can include one or more crystallites. A solid-solution precipitate can be, for example, a single crystallite or can include one or more crystallites. In some cases, an individual discrete particle can be a single crystallite. However, some particles can include multiple crystallites separated by grain boundaries, surface boundaries, and / or amorphous regions. Each crystallite within a material, such as a particle or thin film, can be separated from other crystallites by one or more surfaces, one or more grain boundaries (e.g., dislocations), one or more amorphous regions, one or more regions or volumes with different chemical compositions, one or more regions or volumes with different crystal structures or polymorphs or phases, or any combination of these.

[0059] Individual cubic ZnS crystallites are formed of ZnS having a cubic crystal structure and are substantially (e.g., non-surface or ≦1 nm defects) or completely free of amorphous ZnS and crystalline hexagonal ZnS. In various embodiments herein, each crystalline cubic ZnS particle may only comprise crystalline cubic ZnS and may be substantially free of amorphous ZnS, unstructured cubic ZnS, and hexagonal ZnS (e.g., having less than 50% by weight, less than 25% by weight, less than 10% by weight, less than 5% by weight, less than 1% by weight, less than 0.1% by weight, less than 0.01% by weight, less than 0.005% by weight, less than 0.001% by weight of any combination of amorphous ZnS, unstructured cubic ZnS, and hexagonal ZnS).

[0060] Individual cubic MnS crystallites are formed of MnS having a polymorph or phase cubic crystal structure and are substantially (e.g., non-surface or ≦1 nm defects) or completely free of amorphous MnS and crystalline hexagonal MnS. In various embodiments herein, each crystalline cubic MnS particle may comprise only crystalline cubic MnS and may be substantially free of amorphous MnS, unstructured cubic MnS, and hexagonal MnS (e.g., having less than 50%, less than 25%, less than 10%, less than 5%, less than 1%, less than 0.1%, less than 0.01%, preferably less than 0.005%, more preferably less than 0.001%, by weight of any combination of amorphous MnS, unstructured cubic MnS, and hexagonal MnS).

[0061] The crystallite size and particle size described herein refer to empirically derived crystalline grain and particle size characteristics, which are based on, determined by, or correspond to data from techniques or devices known in the art that can be used to determine crystalline grain size or particle size, such as X-ray diffraction (XRD), electron microscopy (SEM and / or TEM), or light scattering (such as DLS). In embodiments, the size characteristics correspond to physical dimensions such as cross-sectional size (e.g., length, width, thickness, diameter, etc.). In general, the terms "grain boundary", "surface", "crystallite", "amorphous", "unstructured", and "particle" have meanings recognized by those skilled in the art of materials science.

[0062] As used herein, the term "crystallinity" has its usual meaning as understood by those skilled in the art, and refers to the degree of structural order of atoms in a solid material. Highly crystalline materials have a longer range of atomic structural order on average than less crystalline materials. Materials with larger crystallites are characterized by a higher degree of crystallinity on average than materials with smaller crystallites. Crystallinity can be assessed or determined using crystallography techniques to determine material properties, such as one or more X-ray diffraction (XRD) techniques, where the broadening of one or more peaks (or peak widths) in an XRD pattern is inversely correlated with the degree of crystallinity and crystal size. For example, larger crystallites of cubic ZnS (or cubic MnS) will have narrower XRD peaks than smaller crystallites of cubic ZnS (or MnS), when comparing peaks at equivalent peak positions (2θ) and measurements are otherwise performed under identical conditions (e.g., same radiation, same equipment, same temperature, etc.).

[0063] Among other methods, crystallite size can be empirically estimated using a method based on the Scherrer equation, which uses XRD peak widths to calculate crystallite size. The crystallite size of a sample determined based on the Scherrer equation is sometimes referred to as the "Scherrer size." The Scherrer equation (Equation 1) is:

number

[0064] Thus, for various embodiments described herein, the crystallinity of the sulfide additive material may be quantified by one or more indicators, such as by reference to the "Scherrer size" of a sample of the material, by reference to a measurement of the full width at half maximum of the XRD peak width at a peak characteristic of a particular crystalline form, or by other methods or combinations of methods. Crystallite size and / or crystallinity may also be quantified or approximated using other methods, such as electron diffraction, such as transmission electron microscopy (TEM) or scanning electron microscopy (SEM).

[0065] As used herein, the term "crystalline" is used as an adjective to refer to a material or particle that has a sufficiently high degree of crystallinity to achieve a desired sulfide concentration in the electrolyte. In some cases, a sufficiently high degree of crystallinity may be a degree of crystallinity that exceeds a threshold degree of crystallinity as measured by one or more techniques, such as those described above.

[0066] In contrast to "crystalline" materials, the term "unstructured" is used herein as an adjective to refer to materials or particles that have low crystallinity and / or contain a significant amount of amorphous phase material. In some cases, an unstructured material may have a crystallinity below a crystallinity threshold as measured by one or more of the indicators or techniques described above. Alternatively or additionally, an unstructured material may be defined as having an amount of amorphous phase material above a threshold.

[0067] As used herein, the term "unstructured" (e.g., in "unstructured cubic") refers to a characteristic that refers to low, poor, or other undesirable crystallinity of a material for applications contemplated herein, in accordance with the embodiments and descriptions herein, and is not intended to imply that the material is completely or absolutely devoid of atomic structure or crystallinity. As will become more apparent from the discussion below, a material, particle, sample, or other object (such as an unstructured cubic ZnS additive) characterized as "unstructured" may have a structure or crystallinity (e.g., of a cubic phase) that is characterized by a degree of structure or crystallinity that is undesirable for certain embodiments and applications described herein (e.g., low crystallinity, too broad XRD peaks, and / or too small average grain size by Scherrer or Halder-Wagner methods). By way of example only, a ZnS additive characterized by a Scherrer crystallite size less than 100 Angstroms or a non-zero XRD peak having a full width at half maximum value at about 28.6 degrees (2θ, CuK-α) greater than about 0.4 degrees is characterized as unstructured cubic.

[0068] In some cases, the amount of amorphous phase material can be determined or estimated using the same analytical tools described above, such as XRD, TEM, and SEM. Although amorphous phase material does not produce a distinctive peak in XRD, the amount of amorphous phase material in a test sample can be determined by comparing the XRD results to those of samples containing known amounts of crystalline and amorphous material. Alternatively, the approximate amount of amorphous material in a sample may be inferred based on an analysis of the dissolution and reprecipitation behavior. It has been found that when samples containing low crystallinity ZnS and / or amorphous ZnS are placed in KOH electrolyte, the excess dissolved material reprecipitates primarily in the form of hexagonal ZnS, even if some cubic ZnS was present in the pre-dissolved sample. Thus, an iron electrode initially made with a sulfide additive containing cubic ZnS and more than a threshold amount of amorphous ZnS can be expected to have a detectable amount of hexagonal ZnS after a sufficient amount of time (e.g., days, weeks, months, or more after manufacture). Alternatively, the amount of crystalline cubic in the electrode can be determined by the following procedure. An electrode piece is rinsed to remove electrolyte, dried, and analyzed by XRD using a scan rate of 0.5-10 degrees / min and the Rietveld refinement to obtain the mass fraction of cubic ZnS. Multiplying this by the molar mass of zinc divided by the molar mass of ZnS gives mass_Zn_cubic, the mass fraction of the sample that is Zn as cubic ZnS. Another electrode piece is rinsed to remove electrolyte, acid digested, and analyzed by ICP-OES (inductively coupled plasma-optical emission spectroscopy) to obtain mass_Zn_total, the mass fraction that is Zn. The ratio of mass_Zn_cubic / mass_Zn_total is the mass % of the zinc sulfide additive in the form of cubic zinc sulfide.

[0069] Additionally, the present disclosure describes various materials or particles having high or low crystallinity of a particular crystalline phase. The term "unstructured cubic" refers to a particle or material having a cubic phase characterized by low crystallinity, "crystalline cubic" refers to a particle or material having a cubic phase and high crystallinity, "unstructured hexagonal" refers to a particle or material having a hexagonal phase characterized by low crystallinity, and "crystalline hexagonal" refers to a particle or material having a hexagonal phase characterized by high crystallinity.

[0070] Optionally, the term "unstructured cubic" refers to a particle or material having a cubic phase characterized by low crystallinity and / or more than a threshold amount of amorphous material, "crystalline cubic" refers to a particle or material having a cubic phase and high crystallinity and less than a threshold amount of amorphous material, "unstructured hexagonal" refers to a particle or material having a hexagonal phase characterized by low crystallinity and / or more than a threshold amount of amorphous material, and "crystalline hexagonal" refers to a particle or material having a hexagonal phase characterized by high crystallinity and less than a threshold amount of amorphous material.

[0071] For example, in some embodiments, a sample of ZnS or MnS (or other sulfide additive) may be considered "unstructured" if it has a cubic phase characterized by low crystallinity and more than 10% by weight of the sulfide additive material is in the amorphous phase. In other embodiments, the threshold amount of amorphous phase material sufficient to define a sulfide additive material as "unstructured" may be 20%, 25%, 30%, 40%, 50%, 60% or more by weight of the sulfide additive in addition to the sulfide additive material having a cubic phase characterized by low crystallinity.

[0072] Iron electrode batteries with electrolyte concentrations of sulfide that are too low tend to suffer from low rate capacity, capacity fade, high self-discharge rates, and other performance impairments. On the other hand, high concentrations of sulfide in the electrolyte can also result in poor performance due to corrosion or other deleterious effects on the iron electrode.

[0073] Thus, the key to achieving a high performance iron electrode battery is to maintain the concentration of sulfide in the electrolyte within a narrow tolerance range. The inventors have found that the ideal band of sulfide concentrations is from about 0.01 mmol / L to about 10 mmol / L. In some embodiments, the iron electrode battery maintains a sulfide (or S) concentration selected from the range of 0.01±20% mmol / L to 10±20% mmol / L before charging, during charging and / or discharging of the battery and / or when the battery is in an open circuit and / or any other operating state. 2- In some embodiments, the iron electrode battery may include an electrolyte having a Bi concentration lower than that produced by the presence of hexagonal ZnS in contact with the electrolyte and excess Bi 2 S 3 , CuS, PbS, Ir 2 S 3 , and / or higher sulfide (or S) produced by contact of CdS with the electrolyte. 2- ) concentration before charging, during charging and / or discharging of the battery and / or when the battery is in an open circuit and / or any other operating state.

[0074] The life of an iron electrode battery is determined in large part by the time and number of charge-discharge cycles that the battery can maintain the sulfide concentration within this band. To achieve this, both the thermodynamic solubility limit and the kinetic dissolution rate can be managed to maintain the sulfide concentration within an acceptable range, while replacing sulfide lost through conversion to other sulfur species, without providing excess sulfide to the electrolyte. Several methods for achieving a similar goal are described in the Pham Publication '702, cited above.

[0075] The "solubility limit" of a material is the maximum amount (or concentration) of solute that can be dissolved in a solvent at a specified temperature and pressure. If a solution contains a concentration of solute that exceeds the solubility limit, the solute will tend to precipitate. However, the actual concentration of solute in solution at any one time is also a factor in the time-dependent dissolution and / or precipitation rates.

[0076] The soluble sulfide in the electrolyte at a given time can be determined by taking a representative sample from the electrolyte, degassing the sample with argon, combining the sample with a sulfide antioxidant buffer (SAOB) in a 1:1 volume ratio, and measuring the potential of this mixed sample using a sulfide ion selective electrode (ISE) that has been calibrated with a set of standardized sulfide solutions in the appropriate concentration range within the past hour. The standardized sulfide solutions should narrow the range of sulfides of interest. For example, to measure with an accuracy of 1.0E-4M, a suitable standard could cover the range of 10E-6 to 10E-3M. The SAOB is preferably a fresh solution of 500mL of 2M NaOH and 18g of ascorbic acid. Alternatively, total sulfur can be measured using ICP-OES in combination with an additional analytical step that distinguishes between sulfide and oxidized ionic species, such as ion chromatography (IC). Using this second method (ICP-OES+IC or another method), the sulfide concentration is the difference between the total sulfur present in solution and other oxidized sulfur species. Because sulfide is a reactive anion, all analyses should be performed within 4 hours of collection, or samples should be preserved by degassing with argon and then stored under inert gas (i.e., nitrogen, argon) until testing.

[0077] U.S. Patent No. 4,250,236 to Haschka et al. ("Haschka") suggests including sulfide iron electrode additives in the form of "difficult to dissolve" metal sulfides. Specifically, Haschka states that "two examples of [sulfide source additives] are zinc sulfide and manganese sulfide, 'all of whose known polymorphs may be used'" (Haschka, col. 4, lines 29-31, emphasis added). However, as the inventors have discovered, some of the polymorphic forms of ZnS exhibit significantly higher dissolution rates in alkaline solutions than expected, which can result in actual sulfide concentrations that, at least temporarily, far exceed the thermodynamic solubility limit, leading to corrosion of the iron electrode, sulfide loss, and reduced performance over the life of the iron electrode battery.

[0078] Published data and calculations of the solubility of zinc sulfide in 6M KOH alkaline solutions indicate a solubility limit ranging from about 0.02 mM to about 0.7 mM. The inventors' own initial calculations suggest a solubility limit of ZnS in 6M KOH of about 0.3 mM (i.e., 0.0003 moles of sulfide per liter of KOH electrolyte).

[0079] Surprisingly, however, and contrary to the above expectations, the inventors found unexpected dissolution behavior of ZnS in 6M KOH solution. The inventors observed that the apparent solubility limit of ZnS increased with increasing ZnS loading per unit volume of electrolyte, far exceeding the reported solubility limit suggested by the published literature and the inventors' own initial calculations. The results are shown in the data set in Figure 1C. The inventors considered the possibility that ZnS might simply dissolve unexpectedly in 6M KOH, but found another unexpected explanation. Without wishing to be bound by a particular theory of operation, it is believed that some crystalline forms of ZnS produce sulfide concentrations that exceed the expected thermodynamic solubility limit due to differences in the dissolution kinetics of dissolution and reprecipitation of the various crystalline forms of ZnS and / or because the difference in the solubility limits of the different crystalline forms is much larger than expected.

[0080] As shown in Figure 1C, the data suggests that the solubility of unstructured cubic ZnS is highly dependent on the ratio of ZnS solid to electrolyte volume. Although not shown in Figure 1C, hexagonal ZnS (both unstructured hexagonal ZnS and crystalline hexagonal ZnS) was observed to show a similar dependence on solid-liquid ratio. Notably, crystalline cubic ZnS hardly exhibited the same pattern, suggesting it may be more stable and / or less soluble.

[0081] Finally, the data suggest that unstructured cubic ZnS and hexagonal ZnS (both unstructured hexagonal ZnS and crystalline hexagonal ZnS) have a solubility in KOH that is approximately one order of magnitude greater than crystalline cubic ZnS. An alternative explanation is that some polymorphic forms of ZnS actually dissolve so quickly that dissolution outpaces the rate of reprecipitation of ZnS, resulting in sulfide concentrations in solution that substantially exceed the thermodynamic solubility limit of ZnS under the same conditions. We have also found that when ZnS of any crystalline phase dissolves in KOH, it reprecipitates in the faster dissolving hexagonal crystalline form (typically low crystallinity particles). Thus, the fast dissolution and reprecipitation of the fast dissolving crystalline form creates an undesirable dissolution feedback loop that results in undesirably high sulfide concentrations in the electrolyte.

[0082] The inventors have found that both unstructured and highly crystalline particles of the hexagonal wurtzite phase, when dissolved, produce dissolved sulfide concentrations at least one order of magnitude greater than those resulting from the dissolution of highly crystalline particles of the cubic (or sphalerite) phase under otherwise identical conditions. Surprisingly, low-crystalline particles consisting of a unit cell of the cubic phase also exhibited very high dissolution rates, producing solutions with sulfide concentrations substantially exceeding the predicted thermodynamic solubility limit of cubic zinc sulfide. In fact, low-crystalline cubic ZnS particles exhibited dissolution behavior similar to both low-crystalline and high-crystalline hexagonal ZnS particles.

[0083] After the unstructured cubic zinc sulfide was dissolved in the electrolyte solution, excess dissolved zinc sulfide (i.e., above the thermodynamic solubility limit) was reprecipitated as a solid. Unexpectedly, the dissolved sulfide reprecipitated in the form of faster dissolving hexagonal crystals, thereby unnecessarily maintaining a high sulfide concentration in the electrolyte when the hexagonal ZnS particles quickly redissolved.

[0084] In contrast, crystalline cubic zinc sulfide particles demonstrated a substantially slower dissolution rate and lower apparent solubility limit than the non-structured cubic particles, as shown in FIG. 1C.

[0085] Crystalline cubic zinc sulfide with sufficiently high crystallinity is recognized based on full width at half maximum (FWHM) measurements of selected peaks in X-ray diffraction (XRD) scans of zinc sulfide samples. Examples are shown in Figures 2A and 2B. Figure 2A is a schematic of X-ray diffraction spectra representing two sample iron electrodes containing "unstructured" cubic zinc sulfide additive and "crystalline" zinc sulfide additive. In Figure 2A, label 200 represents a peak at 28.6 degrees, label 210 represents a peak at 47.6 degrees, label 220 represents a peak at 56.4 degrees, and label 230 represents a peak at 33.1 degrees. Samples with low crystallinity exhibit broader peaks at positions corresponding to cubic ZnS. Such broad peaks can be quantified in terms of FWHM values, which are larger for less crystalline samples and smaller (narrower) for more crystalline samples. In describing each diffraction peak, reference may be made to the family of parallel crystal lattice planes that give rise to the diffraction peak, represented by Miller indices hkl. The peaks labeled 200, 210, 220, and 230 in FIG. 2A represent cubic zinc sulfide. The 28.6 degree peak labeled 200 has Miller indices (111). The 33.1 degree peak labeled 230 has Miller indices (200). The 47.6 degree peak labeled 210 has Miller indices (220). The 56.4 degree peak labeled 220 has Miller indices (311). Miller indices and peak angles are determined by the Rietveld method for ZnS in the cubic phase. Due to variances in the XRD measurement system, sample preparation, or other variables, the above peak positions may be discriminated to within about + / - 0.1 degrees from the above position values.

[0086] The peak labeled 200 in Figure 2A is shown expanded in Figure 2B. This figure also shows the full width at half maximum (FWHM) measurement, which is a measurement of the width of the curve at half the maximum (peak) of the curve. Due to variance in the XRD measurement system, sample preparation, user variability, or other sources of variability, the measured FWHM value may vary by approximately + / - 0.05 degrees from the stated value. Unless otherwise stated, all XRD peak positions reported herein correspond to 2θ degrees and CuK-α radiation. In measuring peak positions and FWHM, the XRD is scanned at rates ranging from 0.5 to 10 degrees / min, and the data is fitted using the Rietveld method.

[0087] The primary crystalline phases or crystal structures of ZnS are cubic, known as "sphalerite" or "zinc blende", and hexagonal, known as "wurtzite". In some embodiments, the terms "cubic zinc sulfide" and "crystalline cubic zinc sulfide" refer to a zinc sulfide material (e.g., one or more particles) that exhibit non-zero XRD peaks characteristic of cubic zinc sulfide, such as peaks 200, 210, 220, 230 shown in Figures 2A and 3. For example, in some embodiments, crystalline cubic zinc sulfide exhibits one or more non-zero XRD peaks at 2θ angles characteristic of cubic zinc sulfide, such as a non-zero XRD peak at about 28.6 degrees (2θ, CuK-α), with a full width at half maximum value of less than about 0.4 degrees, in other embodiments less than about 0.3 degrees, in other embodiments less than about 0.2 degrees, and in some particular embodiments less than or equal to about 0.17 degrees. Some embodiments of crystalline cubic zinc sulfide may exhibit a non-zero XRD peak at about 47.6 degrees with a FWHM value of less than about 0.5 degrees, in other embodiments less than about 0.4 degrees, in other embodiments less than about 0.3 degrees, and in some specific embodiments, less than about 0.23 degrees. In some embodiments, crystalline cubic zinc sulfide may exhibit a non-zero XRD peak at about 56.4 degrees with a FWHM value of less than about 0.6 degrees, in other embodiments less than about 0.5 degrees, in other embodiments less than about 0.4 degrees, in other embodiments less than about 0.3 degrees, and in some specific embodiments, less than about 0.23 degrees. In other embodiments, "crystalline cubic zinc sulfide" may have a slightly higher FWHM value at one or more of the above peak locations, provided that when at least 0.01 g of granular ZnS material per mL of electrolyte is placed in a 6M KOH electrolyte solution, the material produces a dissolved sulfide concentration of less than about 0.001 moles per liter after 200 hours of soaking time.

[0088] In embodiments, "crystalline cubic ZnS" or "crystalline cubic zinc sulfide" may refer to cubic ZnS (nominally having peaks characteristic of cubic zinc sulfide at 28.6 degrees, 47.6 degrees, and 56.4 degrees 2θ) characterized by one or more of the following: (a) a non-zero XRD at about 28.6 degrees (2θ, CuK-α) with a full width at half maximum of less than about 0.4 degrees, in other embodiments less than about 0.3 degrees, in other embodiments less than about 0.2 degrees, and in some particular embodiments less than or equal to about 0.17 degrees; peak; (b) a non-zero XRD peak at about 47.6 degrees having an FWHM value of less than about 0.5 degrees, in other embodiments less than about 0.4 degrees, in other embodiments less than about 0.3 degrees, and in some specific embodiments, about 0.23 degrees or less; and / or (c) a non-zero XRD peak at about 56.4 degrees having an FWHM value of less than about 0.6 degrees, in other embodiments less than about 0.5 degrees, in other embodiments less than about 0.4 degrees, in other embodiments less than about 0.3 degrees, and in some specific embodiments, about 0.23 degrees or less.

[0089] The term "unstructured cubic ZnS" or "unstructured cubic zinc sulfide" may refer to cubic ZnS that is not or cannot be characterized as crystalline cubic ZnS or highly crystalline cubic ZnS according to the description herein. In embodiments, "unstructured cubic ZnS" or "unstructured cubic zinc sulfide" may refer to cubic ZnS (nominally having peaks characteristic of cubic zinc sulfide at 28.6 degrees, 47.6 degrees, and 56.4 degrees 2θ) characterized by one or more of the following: (a) a non-zero XRD peak at about 28.6 degrees (2θ, CuK-α) with a full width at half maximum value of about 0.4 degrees or greater; (b) a non-zero XRD peak at about 47.6 degrees with a FWHM value of about 0.5 degrees or greater; and / or (c) a non-zero XRD peak at about 56.4 degrees with a FWHM value of about 0.6 degrees or greater. Alternatively or additionally, "non-structured cubic ZnS" or "non-structured cubic zinc sulfide" may refer to ZnS compounds with a particle size ≦25 nm by Scherrer method or ≦12 nm by Halder-Wagner method as measured by XRD. Other techniques for measuring particle size may be used to determine whether the ZnS is "non-structured cubic ZnS" or "non-structured cubic zinc sulfide", including but not limited to transmission electron microscopy and scanning electron microscopy. While different measurement methods may produce different particle size results, the ability to convert particle size approximately between various techniques may be appropriately applied to convert particle size measurements by XRD to the appropriate particle size to determine whether the ZnS material is "non-structured cubic ZnS" or "non-structured cubic zinc sulfide" by other characterization methods.

[0090] Similarly, the terms "unstructured cubic manganese sulfide" and "crystalline cubic manganese sulfide" refer to manganese sulfide materials (e.g., particles(s) or films) that exhibit non-zero XRD peaks characteristic of cubic manganese sulfide. For example, in some embodiments, crystalline cubic manganese sulfide exhibits one or more non-zero XRD peaks at 2θ angles characteristic of cubic manganese sulfide, with full width at half maximum values ​​of less than about 0.6 degrees, in other embodiments less than about 0.4 degrees, in other embodiments less than about 0.3 degrees, and in some particular embodiments, about 0.2 degrees or less.

[0091] As used herein, the term "non-zero XRD peak" refers to a peak that can be found, fitted, detected, or otherwise resolved from or above the background noise or baseline using any of one or more art-known techniques or algorithms for finding, fitting, detecting, or otherwise resolving peaks in a data set. A non-zero XRD peak has a finite FWHM greater than 0 and a finite peak area greater than 0.

[0092] Two samples of untreated ZnS and three samples of ZnS annealed under various conditions were evaluated by XRD and the crystallite size was determined using the Scherrer equation. The untreated sample was found to be "unstructured" ZnS due to the presence of cubic ZnS with low crystallinity and the presence of amorphous phase ZnS. The "treated" sample was found to be sufficiently highly crystalline to produce the desired dissolution characteristics described herein. Data from the same XRD scan was used to calculate the crystallite size of the sample using two methods: a direct application of the Scherrer equation above, and an application of the Halder-Wagner method implemented by Rigaku's PDXL software installed on the X-ray diffractometer used. The data from the above scans are summarized in Tables 1 and 2 below. The two methods produced substantially different absolute values ​​for the same samples, but clear differences can be seen between the structured and crystalline samples within each method. The value of K used in the calculation of the Scherrer equation was 0.9 and the wavelength λ was 1.5406 Angstroms. [Table 1] [Table 2]

[0093] Thus, in some embodiments of the systems and methods herein, ZnS may be sufficiently crystalline (and thus referred to herein as crystalline cubic ZnS, or cubic ZnS characterized by high crystallinity) when the average crystallite size calculated by the Scherrer formula is about 250 Å or more, about 300 Å or more, about 400 Å or more, about 500 Å or more, about 600 Å or more, about 700 Å or more, or about 800 Å or more. Alternatively, in some embodiments of the systems and methods herein, ZnS may be sufficiently crystalline (and thus referred to herein as crystalline cubic ZnS, or cubic ZnS characterized by high crystallinity) when the crystallite size measured by the Halder-Wagner method is about 150 Å or more, about 200 Å or more, about 250 Å or more, about 300 Å or more, about 350 Å or more, or about 400 Å or more.

[0094] In some embodiments, iron electrode batteries may be substantially improved by including only crystalline cubic zinc sulfide particles, such as those exhibiting XRD FWHM values ​​characteristic of crystalline cubic ZnS as described herein, as the sulfide source additive. In various embodiments, crystalline cubic zinc sulfide may be included as an additive in the iron electrode in an amount of about 0.01 to about 20% by weight of the iron electrode. In some particular embodiments, crystalline cubic zinc sulfide may be included as an additive in the iron electrode in an amount of about 0.05 to about 10% by weight of the iron electrode, or about 0.1 to about 5% by weight of the iron electrode. In various embodiments, crystalline cubic zinc sulfide may be included as an additive in the iron electrode in a particle size of about 0.1 microns to about 500 microns, or in some embodiments, about 0.1 microns to about 20 microns, or about 1 to 10 microns.

[0095] Having a crystalline cubic zinc sulfide and / or crystalline cubic manganese sulfide additive (wherein the additive is substantially free of or completely free of amorphous zinc sulfide, amorphous manganese sulfide, non-structured zinc sulfide, non-structured manganese sulfide, hexagonal zinc sulfide, and / or hexagonal manganese sulfide) in an iron electrode battery is contemplated herein to improve battery performance in multiple metrics. For example, batteries with cubic zinc sulfide on the iron electrode tend to achieve improved cycle life, increased number of high discharge rate cycles (1C, 2C, 3C, or faster discharge rates), improved energy efficiency, improved coulombic efficiency, improved charge retention, reduced self-discharge rate, and improved performance at high temperatures (e.g., as measured by any of the metrics discussed above). In some embodiments, the use of only highly crystalline cubic zinc sulfide and / or highly crystalline cubic manganese sulfide instead of unstructured cubic or hexagonal zinc sulfide and / or manganese sulfide may improve and / or simplify the electrode manufacturing process by reducing the solubility of the metal sulfide additive at intermediate processing steps. Iron electrodes incorporating crystalline cubic zinc sulfide and / or crystalline cubic manganese sulfide can be manufactured by any suitable process, such as hot pressing, cold pressing, sintering, wet paste lamination, dry pressing, slurry coating, PTFE-based processes, roll bonding, tape casting (blade coating) pocket filling, or a combination of these processes.

[0096] In some embodiments, crystalline cubic manganese sulfide (manganite) can be used in place of or in combination with zinc sulfide in iron electrode batteries. Crystalline cubic manganese sulfide (MnS) is expected to produce similar sulfide concentrations as crystalline cubic zinc sulfide (ZnS) when dissolved in alkaline battery electrolyte. As above, crystalline cubic MnS can be distinguished from other crystalline forms of MnS by evaluating the FWHM values ​​of selected peaks in an X-ray diffraction analysis of a sample of the material.

[0097] In some embodiments, instead of or in addition to crystalline cubic zinc sulfide or cubic manganese sulfide as an additive in the iron electrode, a quantity of crystalline cubic zinc sulfide or cubic manganese sulfide may be used as a sulfide source material in the iron electrode battery that is exposed to the electrolyte but is physically and electrically disconnected from the iron electrode. The sulfide source material added to the electrolyte without being electrically connected to the iron electrode may be referred to herein as a "sulfide reservoir."

[0098] The sulfide additives described herein have crystalline cubic ZnS and / or crystalline cubic MnS and may be added to the iron electrode (e.g., combined with, added to, mixed with the iron active material) during the manufacture of the iron electrode or a battery having an iron electrode. The sulfide additives may also be introduced in a manner that allows for subsequent activation by electrochemical or chemical methods. Optionally, the iron electrode disclosed herein may include any combination of crystalline cubic ZnS and crystalline cubic MnS. Optionally, the iron electrode may include low solubility sulfide phases such as antimony sulfide, bismuth sulfide, cadmium sulfide, cerium sulfide, cobalt sulfide, copper sulfide, copper disulfide, indium sulfide, iron sulfide, iron disulfide, lead sulfide, manganese disulfide, mercury sulfide, molybdenum disulfide, nickel sulfide, silver disulfide, and tin sulfide. For example, iron electrodes may include iron sulfide, manganese sulfide, tin sulfide, and zinc sulfide. ZnS and MnS materials may contain impurities. The impurity content may be <2%, or <1%, or <0.5%, or <0.1%, or <0.01% by mass. Impurities may be present as dopants in the cubic ZnS lattice. Such dopants may cause a slight shift in the Bragg peak angle and / or a broadening of the FWHM.

[0099] In various embodiments, crystalline cubic zinc sulfide can be produced by various processes depending on one or more starting raw materials or materials. For example, one method of making crystalline cubic zinc sulfide from a zinc sulfide starting material of unknown crystal morphology and crystallinity includes evaluating the starting material to determine the crystalline phase(s) and crystallinity of the starting material. As described above, the crystalline phase(s) of the starting material is determined by the position of the XRD peak in the XRD scan. The FWHM value of the peak corresponding to a given crystalline phase can be used to evaluate the crystallinity. Thus, zinc sulfide having a peak at the above position and an FWHM value within the above range may already be usable for iron electrode batteries.

[0100] However, if the FWHM value is too large (corresponding to a broader peak and therefore undesirably less crystalline or undesirably low average crystallite size), the starting material may be heat treated to increase the crystallinity and / or average crystallite size. Such heat treatment involves annealing the starting material by heating in a vacuum or inert atmosphere (e.g., nitrogen, argon, or other inert gas) to an elevated temperature of at least about 400° C. but below the melting point of ZnS, about 1850° C., for at least about 5 seconds or for several hours, and then slowly cooling the material to room temperature. In some embodiments, the heat treatment may involve holding the material at a constant or varying elevated temperature for 30 minutes, 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, or more. In some specific embodiments, the heat treatment involves heating the material to a temperature of 800° C. to about 900° C., holding for about 10 minutes to 20 minutes, and then slowly cooling the material to room temperature. In some embodiments, heating and / or cooling may be performed at a relatively slow rate, such as, in some embodiments, at a heating rate of about 10° C. / min, or in some embodiments, at about 5° C. / min, or in some embodiments, at a heating rate of less than 5° C. / min. In some embodiments, cooling to room temperature may occur by natural convection without controlling the rate of temperature drop.

[0101] Alternatively, amorphous ZnS (and / or MnS), unstructured or low crystallinity cubic ZnS (and / or MnS), and / or hexagonal ZnS (and / or MnS) starting materials may be heat treated under conditions necessary to form and / or grow a cubic crystal structure to form the preferred high crystallinity crystalline cubic ZnS (and / or MnS) as described herein. In various embodiments, heat treatment of the ZnS and / or MnS materials may be performed before, during, or after fabrication of the iron-electrode.

[0102] In some embodiments, crystalline cubic zinc sulfide may be made from raw materials that include zinc and sulfur. For example, in some embodiments, solid zinc sulfide may be chemically precipitated from an aqueous solution containing dissolved zinc and dissolved sulfur (from any suitable source material). In some embodiments, the conditions of the precipitation reaction, such as temperature, reactant concentration, or inclusion of other additives, may be selected and controlled to produce a crystalline cubic zinc sulfide precipitate. In other embodiments, the precipitation reaction may be used to produce solid amorphous, unstructured, or low crystallinity zinc sulfide particles, which may then be heat treated as described herein to produce substantially only crystalline cubic zinc sulfide.

[0103] In other embodiments, crystalline cubic zinc sulfide may be made from a solid state reaction using small particulate (e.g., less than about 20 microns) solid zinc and sulfur raw materials at high temperatures (e.g., above 500° C.) and under vacuum or inert atmosphere.

[0104] In various embodiments, crystalline cubic MnS may be made using the same methods described above for making crystalline cubic ZnS. That is, crystalline cubic MnS may be made by annealing amorphous, unstructured, and / or low crystallinity cubic MnS and / or hexagonal MnS at a temperature sufficient to achieve crystalline cubic MnS. Alternatively, crystalline cubic MnS may be made by controlling the rate at which MnS precipitates from a solution containing dissolved Mn and S species, or by high temperature (e.g., above about 500° C.) reaction of Mn and S solids in a vacuum or inert atmosphere.

[0105] Various embodiments may include an electrochemical cell, such as a battery (e.g., 100, 10) having an iron negative electrode (also called an iron anode) and an electrolyte (e.g., 102, 103, 20) having a total hydroxide concentration of more than 3M. In some embodiments, the electrolyte may have a total hydroxide concentration of more than 3M, at or above the solubility limit of hydroxide in the electrolyte. In some embodiments, the total hydroxide concentration is more than 3M, including more than 3M KOH+NaOH and more than 0.01M LiOH therein. In some embodiments, the electrolyte may have a total hydroxide concentration of 11M or less therein. In some embodiments, the electrolyte may have a total hydroxide concentration of 11M or less, or 1M LiOH or 10M KOH+NaOH or less therein. In some embodiments, if the electrolyte is KOH-based, the total hydroxide concentration may be more than 4M and less than 10M. However, the present disclosure is not limited to any particular electrolyte concentration.

[0106] As used herein, unless otherwise specified, the term "specific gravity", also called apparent density, should be given the broadest possible meaning and is generally intended to mean the weight per unit volume of a structure, e.g., a volumetric form of a material. This property will include the internal porosity of the particle as a fraction of its volume. It can be measured, among other techniques, with a low viscosity fluid that wets the particle surface.

[0107] As used herein, unless otherwise specified, the term "actual density," which may also be referred to as true density, should be given the broadest possible meaning and generally refers to the weight per unit volume of a material if no voids were present in that material. This measurement and characterization essentially excludes internal porosity from the material, e.g., does not include any voids in the material.

[0108] Thus, a collection of porous foam balls (e.g., Nerf® balls) can be used to illustrate the relationship between the three density properties. The weight of the ball filling a container would be the bulk density of the ball:

number

[0109] The weight of a single ball per spherical volume of the ball would be its apparent density.

number

[0110] The weight of the material that makes up the ball's skeleton, i.e., with all void volume removed, per remaining volume of that material would be the skeleton density.

number

[0111] Various embodiments are discussed with respect to the use of iron as a component of a battery (or cell) (e.g., 100, 10), as a material in a battery (or cell) (e.g., 100, 10), such as an electrode, and combinations and variations thereof. In various embodiments, the iron material may be an iron powder, such as a gas or water atomized powder or sponge iron powder. In various embodiments, the iron material may be in the form of pellets, which may be spherical or substantially spherical. In various embodiments, the iron material may be porous and may contain open and / or closed internal pores. In various embodiments, the iron material may include materials that have been further processed by hot or cold briquetting. An embodiment of an iron material for use in various embodiments described herein, including for use as an electrode material, may have one, more than one, or all of the material properties as set forth in Table 3 below. As used herein, including in Table 3, the following terms have the following meanings, unless expressly stated otherwise: "specific surface area" means the total surface area of ​​a material per unit mass, including the surface area of ​​pores in a porous structure; "total Fe (wt%)" means the mass percent of total iron relative to the total mass of the iron material; "metallic Fe (wt%)" means the mass percent of Fe relative to the total mass of the iron material. 0 The mass percentage of iron in the iron-rich state is 0.01%. [Table 3]

[0112] * The specific surface area is preferably determined by the Brunauer-Emmett-Teller adsorption method ("BET"), more preferably BET as set forth in ISO 9277, the disclosure of which is incorporated herein by reference in its entirety. It is recognized that other tests, such as methylene blue (MB) staining, ethylene glycol monoethyl ether (EGME) adsorption, electrokinetic analysis of complex ion adsorption, and protein retention (PR) methods, can be used to provide results that can be correlated with the BET results.

[0113] **Skeletal density is preferably determined by helium (He) pycnometer method, more preferably as set forth in ISO 12154, the disclosure of which is incorporated herein by reference in its entirety. It is recognized that other tests can be used to provide results that can be correlated with He pycnometer results. Skeletal density is sometimes also referred to in the art as "true density" or "actual density."

[0114] *** Apparent density is preferably determined by immersion in water, more preferably as set forth in ISO 15968, the disclosure of which is incorporated herein by reference in its entirety. It is recognized that other tests can be used to provide results that can be correlated with He pycnometer results. Porosity can be defined as the ratio of apparent density to actual density.

number

[0115] #Total Fe (wt%) is preferably determined by dichromate titration, more preferably as set forth in ASTM E246-10, the disclosure of which is incorporated herein by reference in its entirety. It is recognized that other tests, such as tin(II) chloride reduction titration, titanium(III) chloride reduction titration, and inductively coupled plasma (ICP) spectroscopy, can be used to provide results that can be correlated to the dichromate titration.

[0116] ##Metallic Fe (wt%) is preferably determined by iron(III) chloride titration, more preferably as set forth in ISO 16878, the disclosure of which is incorporated herein by reference in its entirety. It is recognized that other tests, such as bromine-methanol titration, can be used to provide results that can be correlated to iron(III) chloride titration.

[0117] Various embodiments are discussed with respect to the use of direct reduced iron (DRI) as a battery (or cell) material, as a battery (or cell) component, and combinations and variations thereof. In various embodiments, DRI may be produced from or may be material resulting from the reduction of natural or processed iron ore, such reduction being carried out without reaching the melting temperature of iron. In various embodiments, the iron ore may be taconite or magnetite or hematite or goethite, etc. In various embodiments, DRI may be in the form of pellets, which may be spherical or substantially spherical. In various embodiments, DRI may be porous and may contain open and / or closed internal pores. In various embodiments, DRI may include material that has been further processed by hot or cold briquetting. In various embodiments, DRI is produced by reducing iron ore pellets to produce ferrous metal (Fe 0DRI can be produced by forming more metallic (more reduced, less oxidized) materials such as iron ore taconite, wustite (FeO), or composite pellets containing iron metal and residual oxide phases. In various non-limiting embodiments, DRI may be reduced iron ore taconite, direct reduced ("DR") taconite, reduced "blast furnace (BF) grade" pellets, reduced "electric arc furnace (EAF) grade" pellets, "cold direct reduced iron (CDRI)" pellets, direct reduced iron ("DRI") pellets, hot briquetted iron (HBI), or any combination thereof. In the iron and steel industry, DRI is sometimes referred to as "sponge iron" and its use is particularly common in India. An embodiment of an iron material, including an exemplary embodiment of a DRI material for use in various embodiments described herein, including for use as an electrode material, may have one, more than one, or all of the material properties as set forth in Table 4 below. As used herein, including in Table 4, the following terms have the following meanings, unless expressly stated otherwise: "specific surface area" means the total surface area of ​​a material per unit mass, including the surface area of ​​pores in a porous structure; "carbon content" or "carbon (wt%)" means the mass of total carbon as a percentage of the total mass of the DRI; "cementite content" or "cementite (wt%)" means the mass of Fe as a percentage of the total mass of the DRI. 3 "Total Fe (wt%)" means the mass of all iron as a percentage of the total mass of the DRI; "Metallic Fe (wt%)" means the mass of Fe as a percentage of the total mass of the DRI. 0 "Metallization" means the mass of iron in the Fe state as a percentage of the total mass of iron. 0 As used herein, weight and volume percentages and apparent densities are understood to exclude any pore-infiltrating electrolyte or transient additives within the pores, unless otherwise stated.

[0118] Various embodiments may provide devices and / or methods for use in bulk energy storage systems, such as long-term energy storage (LODES) systems, short-term energy storage (SDES) systems, etc. For example, various embodiments may provide batteries for bulk energy storage systems, such as batteries for LODES systems, batteries for SDES systems, and / or batteries for systems that require power supply of any duration. Renewable energy sources are becoming increasingly prevalent and cost-effective. However, many renewable energy sources face intermittency issues that hinder the adoption of renewable energy sources. The impact of renewable energy sources' tendency to be intermittent can be mitigated by pairing them with bulk energy storage systems, such as LODES systems, SDES systems, etc. To support the adoption of combined generation, transmission, and storage systems (e.g., renewable generation sources paired with bulk energy storage systems, and power plants with transmission facilities in either the power plant and / or the bulk energy storage system), devices and methods are needed to support the design and operation of such combined generation, transmission, and storage systems, such as the various embodiment devices and methods described herein.

[0119] A combined generation, transmission, and storage system may be a power plant that includes one or more generation sources (e.g., one or more renewable generation sources, one or more non-renewable generation sources, a combination of renewable and non-renewable generation sources, etc.), one or more transmission facilities, and one or more bulk energy storage systems. The transmission facilities in either the power plant and / or the bulk energy storage systems may be co-optimized with the generation and storage systems or may impose constraints on the design and operation of the generation and storage systems. The combined generation, transmission, and storage system may be configured to meet various output targets under various design and operational constraints.

[0120] 4-12 show various exemplary systems in which one or more aspects of various embodiments can be used as part of a bulk energy storage system, such as a LODES system, an SDES system, a system requiring power supply for any period of time, etc. For example, various embodiments described herein with reference to FIGS. 1A-3, such as electrochemical cells (or batteries) 100, 10, can be used as batteries for bulk energy storage systems, such as a LODES system, an SDES system, a system requiring power supply for any period of time, and / or various electrodes described herein can be used as components of a bulk energy storage system. As used herein, the term "LODES system" refers to a bulk energy storage system configured to have a rated duration (energy / power ratio) of 24 hours (h) or longer, such as a duration of 24 hours, a duration of 24 hours to 50 hours, a duration of more than 50 hours, a duration of 24 hours to 150 hours, a duration of more than 150 hours, a duration of 24 hours to 200 hours, a duration of more than 200 hours, a duration of 24 hours to 500 hours, a duration of more than 500 hours, etc. As a further example, various embodiments of the electrochemical cells (or batteries) 100, 10, etc. described herein with reference to Figures 1A-3 can be used as batteries for backup power systems, such as backup power systems for telecommunications, data centers, electronic devices, traffic signals, medical facilities, or buildings. The duration of power delivery from the electrochemical cells (or batteries) 100, 10 can be any duration. The durations of energy storage and / or power delivery described herein, generally, and with reference to Figures 4-12 in particular, are provided by way of example only and are not intended to be limiting.

[0121] FIG. 4 illustrates an exemplary system in which one or more aspects of the various embodiments may be used as part of a bulk energy storage system. Although FIG. 4 is discussed in relation to an example LODES system 304, the duration of energy storage and / or power delivery described with reference to FIG. 4 is provided by way of example only and is not intended to limit the scope of the present invention or claims. As a specific example, a bulk energy storage system incorporating one or more aspects of the various embodiments may be a LODES system 304. As an example, the LODES system 304 may include the batteries of the various embodiments described herein, the various electrodes described herein, and the like. The LODES system 304 may be electrically connected to a wind farm 302 and one or more transmission facilities 306. The wind farm 302 may be electrically connected to the transmission facility 306. The transmission facility 306 may be electrically connected to a power grid 308. The wind farm 302 may generate power, and the wind farm 302 may output the generated power to the LODES system 304 and / or the transmission facility 306. The LODES system 304 can store power received from the wind farm 302 and / or the transmission facility 306. The LODES system 304 can output the stored power to the transmission facility 306. The transmission facility 306 can output power received from one or both of the wind farm 302 and the LODES system 304 to the grid 308 and / or can receive power from the grid 308 and output the power to the LODES system 304. The wind farm 302, the LODES system 304, and the transmission facility 306 together can form a power plant 300, which may be a combined power, transmission, and storage system. Power generated by the wind farm 302 can be fed directly to the grid 308 via the transmission facility 306 or can be stored in the LODES system 304 first.In certain cases, the power provided to the grid 308 may be entirely from the wind farm 302, entirely from the LODES system 304, or from a combination of the wind farm 302 and the LODES system 304. The distribution of power from the combined wind farm 302 and LODES system 304 power plant 300 may be controlled according to a predetermined long-term (multi-day or even multi-year) schedule, or according to a day-ahead (24-hour notice) market, or according to an hour-ahead market, or in response to real-time pricing signals.

[0122] As one example of the operation of the power plant 300, the LODES system 304 can be used to reshape and "stabilize" the power produced by the wind farm 302. In one such example, the wind farm 302 may have a peak power output (capacity) of 260 megawatts (MW) and a capacity factor (CF) of 41%. The LODES system 304 may have a power rating (capacity) of 106 MW, a rated duration (energy / power ratio) of 150 hours (h), and a rated energy of 15,900 megawatt hours (MWh). In another such example, the wind farm 302 may have a peak power output (capacity) of 300 MW and a capacity factor (CF) of 41%. The LODES system 304 may have a power rating (capacity) of 106 MW, a rated duration (energy / power ratio) of 200 hours, and a rated energy of 21,200 MWh. In another such example, the wind farm 302 may have a peak power output (capacity) of 176 MW and a capacity factor (CF) of 53%. The LODES system 304 may have a power rating (capacity) of 88 MW, a rated duration (energy / power ratio) of 150 hours, and a rated energy of 13,200 MWh. In another such example, the wind farm 302 may have a peak power output (capacity) of 277 MW and a capacity factor (CF) of 41%. The LODES system 304 may have a power rating (capacity) of 97 MW, a rated duration (energy / power ratio) of 50 hours, and a rated energy of 4,850 MWh. In another such example, the wind farm 302 may have a peak power output (capacity) of 315 MW and a capacity factor (CF) of 41%. The LODES system 304 may have a power rating (capacity) of 110 MW, a rated duration (energy / power ratio) of 25 hours, and a rated energy of 2,750 MWh.

[0123] FIG. 5 illustrates an exemplary system in which one or more aspects of the various embodiments may be used as part of a bulk energy storage system. Although FIG. 5 is discussed in relation to an example LODES system 304, the duration of energy storage and / or power delivery described with reference to FIG. 5 is provided merely as an example and is not intended to limit the scope of the present invention or claims. As a specific example, a bulk energy storage system incorporating one or more aspects of the various embodiments may be a LODES system 304. As an example, the LODES system 304 may include the batteries of the various embodiments described herein, the various electrodes described herein, and the like. The system of FIG. 5 may be similar to the system of FIG. 4, except that a photovoltaic (PV) station 402 may be used in place of the wind power station 302. The LODES system 304 may be electrically connected to the PV station 402 and one or more transmission facilities 306. The PV station 402 may be electrically connected to the transmission facility 306. The transmission facility 306 may be electrically connected to the power grid 308. The PV station 402 can generate power, and the PV station 402 can output the generated power to the LODES system 304 and / or the transmission facility 306. The LODES system 304 can store power received from the PV station 402 and / or the transmission facility 306. The LODES system 304 can output the stored power to the transmission facility 306. The transmission facility 306 can output power received from one or both of the PV station 402 and the LODES system 304 to the grid 308 and / or can receive power from the grid 308 and output the power to the LODES system 304. The PV station 402, the LODES system 304, and the transmission facility 306 together can comprise a power plant 400, which may be a combined generation, transmission, and storage system. The power generated by the PV station 402 may be fed directly into the power grid 308 via the transmission facility 306 or may first be stored in the LODES system 304 .In certain cases, the power provided to the grid 308 may be delivered entirely from the PV stations 402, entirely from the LODES systems 304, or from a combination of PV stations 402 and LODES systems 304. The delivery of power from the combined PV stations 402 and LODES systems 304 power plant 400 may be controlled according to a predetermined long-term (multi-day or even multi-year) schedule, or according to a day-ahead (24-hour notice) market, or according to an hour-ahead market, or in response to real-time pricing signals.

[0124] As one example of the operation of the power plant 400, the LODES system 304 may be used to reshape and "stabilize" the power produced by the PV station 402. In one such example, the PV station 402 may have a peak power output (capacity) of 490 MW and a capacity factor (CF) of 24%. The LODES system 304 may have a power rating (capacity) of 340 MW, a rated duration (energy / power ratio) of 150 hours, and a rated energy of 51,000 MWh. In another such example, the PV station 402 may have a peak power output (capacity) of 680 MW and a capacity factor (CF) of 24%. The LODES system 304 may have a power rating (capacity) of 410 MW, a rated duration (energy / power ratio) of 200 hours, and a rated energy of 82,000 MWh. In another such example, the PV station 402 may have a peak power output (capacity) of 330 MW and a capacity factor (CF) of 31%. The LODES system 304 may have a power rating (capacity) of 215 MW, a rated duration (energy / power ratio) of 150 hours, and a rated energy of 32,250 MWh. In another such example, the PV station 402 may have a peak power output (capacity) of 510 MW and a capacity factor (CF) of 24%. The LODES system 304 may have a power rating (capacity) of 380 MW, a rated duration (energy / power ratio) of 50 hours, and a rated energy of 19,000 MWh. In another such example, the PV station 402 may have a peak power output (capacity) of 630 MW and a capacity factor (CF) of 24%. The LODES system 304 may have a power rating (capacity) of 380 MW, a rated duration (energy / power ratio) of 25 hours, and a rated energy of 9,500 MWh.

[0125] FIG. 6 illustrates an exemplary system in which one or more aspects of the various embodiments may be used as part of a bulk energy storage system. Although FIG. 6 is discussed in relation to an example LODES system 304, the duration of energy storage and / or power delivery described with reference to FIG. 6 is provided merely as an example and is not intended to limit the scope of the present invention or claims. As a specific example, a bulk energy storage system incorporating one or more aspects of the various embodiments may be a LODES system 304. As an example, the LODES system 304 may include the batteries of the various embodiments described herein, the various electrodes described herein, and the like. The system of FIG. 6 may be similar to the systems of FIG. 4 and FIG. 5, except that the wind farm 302 and the photovoltaic (PV) farm 402 may both be power generating devices operating together in a power plant 500. The PV farm 402, the wind farm 302, the LODES system 304, and the transmission facility 306 may together comprise a power plant 500, which may be a combined power generation, transmission, and storage system. Electricity generated by the PV sites 402 and / or wind farms 302 may be fed directly into the grid 308 via the transmission facility 306 or may first be stored in the LODES system 304. In certain cases, the electricity provided to the grid 308 may be fed entirely from the PV sites 402, entirely from the wind farms 302, entirely from the LODES system 304, or from a combination of the PV sites 402, the wind farms 302, and the LODES system 304. The delivery of electricity from the combined wind farms 302, the PV sites 402, and the LODES system 304 power plant 500 may be controlled according to a predetermined long-term (multi-day or even multi-year) schedule, or according to a day-ahead (24-hour notice) market, or according to an hour-ahead market, or in response to real-time pricing signals.

[0126] As one example of the operation of the power plant 500, the LODES system 304 can be used to reshape and "stabilize" the power produced by the wind farm 302 and the PV farm 402. In one such example, the wind farm 302 may have a peak power output (capacity) of 126 MW and a capacity factor (CF) of 41%, and the PV farm 402 may have a peak power output (capacity) of 126 MW and a capacity factor (CF) of 24%. The LODES system 304 may have a power rating (capacity) of 63 MW, a rated duration (energy / power ratio) of 150 hours, and a rated energy of 9,450 MWh. In another such example, the wind farm 302 may have a peak power output (capacity) of 170 MW and a capacity factor (CF) of 41%, and the PV farm 402 may have a peak power output (capacity) of 110 MW and a capacity factor (CF) of 24%. The LODES system 304 may have a power rating (capacity) of 57 MW, a rated duration (energy / power ratio) of 200 hours, and a rated energy of 11,400 MWh. In another such example, the wind farm 302 may have a peak power output (capacity) of 105 MW and a capacity factor (CF) of 51%, and the PV farm 402 may have a peak power output (capacity) of 70 MW and a capacity factor (CF) of 31%. The LODES system 304 may have a power rating (capacity) of 61 MW, a rated duration (energy / power ratio) of 150 hours, and a rated energy of 9,150 MWh. In another such example, the wind farm 302 may have a peak power output (capacity) of 135 MW and a capacity factor (CF) of 41%, and the PV farm 402 may have a peak power output (capacity) of 90 MW and a capacity factor (CF) of 24%. The LODES system 304 may have a power rating (capacity) of 68 MW, a rated duration (energy / power ratio) of 50 hours, and a rated energy of 3,400 MWh. In another such example, the wind farm 302 may have a peak power output (capacity) of 144 MW and a capacity factor (CF) of 41%, and the PV farm 402 may have a peak power output (capacity) of 96 MW and a capacity factor (CF) of 24%.The LODES system 304 may have a power rating (capacity) of 72 MW, a rated duration (energy / power ratio) of 25 hours, and a rated energy of 1,800 MWh.

[0127] FIG. 7 illustrates an exemplary system in which one or more aspects of the various embodiments may be used as part of a bulk energy storage system. Although FIG. 7 is discussed in relation to an example LODES system 304, the duration of energy storage and / or power delivery described with reference to FIG. 7 is provided by way of example only and is not intended to limit the scope of the present invention or claims. As a specific example, a bulk energy storage system incorporating one or more aspects of the various embodiments may be a LODES system 304. As an example, the LODES system 304 may include the batteries of the various embodiments described herein, the various electrodes described herein, and the like. The LODES system 304 may be electrically connected to one or more transmission facilities 306. In this manner, the LODES system 304 may operate in a "standalone" manner to arbitrate energy near market prices and / or avoid transmission constraints. The LODES system 304 may be electrically connected to one or more transmission facilities 306. The transmission facilities 306 may be electrically connected to a power grid 308. The LODES system 304 may store the power received from the transmission facility 306. The LODES system 304 may output the stored power to the transmission facility 306. The transmission facility 306 may output the power received from the LODES system 304 to the power grid 308 and / or may receive power from the power grid 308 and output the power to the LODES system 304.

[0128] The LODES system 304 and the transmission facility 306 together can constitute a power generation plant 900. As an example, the power generation plant 900 may be located downstream of the transmission constraints, close to the power consumption. In such an example downstream power generation plant 600, the LODES system 304 may have a duration of 24 to 500 hours and may perform full discharges once or multiple times a year to support peak power consumption at times when the transmission capacity is not sufficient to serve customers. In addition, in such an example downstream power generation plant 600, the LODES system 304 may perform several shallow discharges (daily or more frequently) to arbitrage the difference between nighttime and daytime electricity prices and reduce the overall cost of electricity service to customers. As a further example, the power plant 600 may be located upstream of a transmission constraint, close to the generation. In such an example upstream power plant 600, the LODES system 304 may have a duration of 24 hours to 500 hours and may undergo one or more full charges per year to absorb excess generation at times when transmission capacity is insufficient to distribute electricity to customers. In addition, in such an example upstream power plant 600, the LODES system 304 may undergo several shallow charges and discharges (daily or more frequently) to arbitrage the difference between nighttime and daytime electricity prices and maximize the value of the power generation facility's output.

[0129] FIG. 8 illustrates an exemplary system in which one or more aspects of the various embodiments may be used as part of a bulk energy storage system. Although FIG. 8 is discussed in relation to an example LODES system 304, the duration of energy storage and / or power delivery described with reference to FIG. 8 is provided by way of example only and is not intended to limit the scope of the present invention or claims. As a specific example, a bulk energy storage system incorporating one or more aspects of the various embodiments may be a LODES system 304. As an example, the LODES system 304 may include the batteries of the various embodiments described herein, the various electrodes described herein, and the like. The LODES system 304 may be electrically connected to commercial and industrial (C&I) customers 702, such as data centers, factories, and the like. The LODES system 304 may be electrically connected to one or more transmission facilities 306. The transmission facilities 306 may be electrically connected to a power grid 308. The transmission facilities 306 may receive power from the power grid 308 and output the power to the LODES system 304. The LODES system 304 may store the power received from the transmission facility 306. The LODES system 304 may output the stored power to the C&I customers 702. In this manner, the LODES system 304 may operate to reshape the power purchased from the grid 308 to match the consumption patterns of the C&I customers 702.

[0130] The LODES system 304 and the transmission facility 306 together may comprise a power generation plant 700. As an example, the power generation plant 700 may be located near the electricity consumption, i.e., near the C&I customers 702, such as between the power distribution grid 308 and the C&I customers 702. In such an example, the LODES system 304 may have a duration of 24 hours to 500 hours and may purchase power from the market at a time when power is cheaper, thereby charging the LODES system 304. The LODES system 304 may then discharge and provide power to the C&I customers 702 at a time when the market price is higher, thus offsetting the market purchases of the C&I customers 702. As an alternative configuration, the power generation plant 700 may be located not between the power distribution grid 308 and the C&I customers 702, but between a renewable resource, such as a PV site, a wind farm, etc., and the transmission facility 306, which may be connected to the renewable resource. In such an alternative example, the LODES system 304 may have a duration between 24 hours and 500 hours, and the LODES system 304 may be charged at a time when renewable output may be available. The LODES system 304 may then discharge to cover some or all of the C&I customers 702's power needs and provide the C&I customers 702 with renewable energy derived electricity.

[0131] FIG. 9 illustrates an exemplary system in which one or more aspects of the various embodiments may be used as part of a bulk energy storage system. Although FIG. 9 is discussed in relation to an example LODES system 304, the duration of energy storage and / or power delivery described with reference to FIG. 9 is provided by way of example only and is not intended to limit the scope of the present invention or claims. As a specific example, a bulk energy storage system incorporating one or more aspects of the various embodiments may be a LODES system 304. As an example, the LODES system 304 may include the batteries of the various embodiments described herein, the various electrodes described herein, and the like. The LODES system 304 may be electrically connected to a wind farm 302 and one or more transmission facilities 306. The wind farm 302 may be electrically connected to the transmission facility 306. The transmission facility 306 may be electrically connected to a C&I customer 702. The wind farm 302 may generate power, and the wind farm 302 may output the generated power to the LODES system 304 and / or the transmission facility 306. The LODES system 304 may store the power received from the wind farm 302 .

[0132] The LODES system 304 can output the stored power to the transmission facility 306. The transmission facility 306 can output the power received from one or both of the wind farm 302 and the LODES system 304 to the C&I customer 702. The wind farm 302, the LODES system 304, and the transmission facility 306 can together comprise a power plant 800, which may be a combined generation, transmission, and storage system. The power generated by the wind farm 302 can be delivered directly to the C&I customer 702 via the transmission facility 306, or it can first be stored in the LODES system 304. In certain cases, the power provided to the C&I customer 702 can be delivered entirely from the wind farm 302, entirely from the LODES system 304, or from a combination of the wind farm 302 and the LODES system 304. The LODES system 304 may be used to reshape electricity generated by the wind farm 302 to match the consumption patterns of the C&I customers 702. In one such example, the LODES system 304 may have a duration of 24 hours to 500 hours and may charge when renewable generation by the wind farm 302 exceeds the C&I customers 702 loads. The LODES system 304 may then discharge when renewable generation by the wind farm 302 falls below the C&I customers 702 loads to provide the C&I customers 702 with a stable renewable profile that offsets some or all of the C&I customers 702 electricity consumption.

[0133] FIG. 10 illustrates an exemplary system in which one or more aspects of the various embodiments may be used as part of a bulk energy storage system. Although FIG. 10 is discussed in relation to an example LODES system 304, the duration of energy storage and / or power supply described with reference to FIG. 10 is provided by way of example only and is not intended to limit the scope of the present invention or claims. As a specific example, a bulk energy storage system incorporating one or more aspects of the various embodiments may be a LODES system 304. As an example, the LODES system 304 may include the batteries of the various embodiments described herein, the various electrodes described herein, and the like. The LODES system 304 may be part of a power plant 900 that integrates a large amount of renewable generation into a microgrid, for example, by matching the output of renewable generation by the PV site 402 and the wind power site 302 with existing thermal generation by, for example, a thermal power plant 902 (e.g., a gas plant, a coal plant, a diesel generator set, and the like, or a combination of thermal generation methods), and where the renewable generation and thermal generation serve the C&I customer 702 loads when availability is high. A microgrid, such as the microgrid comprised of power plant 900 and thermal power plant 902, may provide an availability rate of 90% or higher. Power generated by PV site 402 and / or wind power site 302 may be delivered directly to C&I customers 702 or may first be stored in LODES system 304.

[0134] In a particular case, the power provided to the C&I customers 702 may be entirely from the PV sites 402, entirely from the wind farms 302, entirely from the LODES systems 304, entirely from the thermal power plants 902, or any combination of the PV sites 402, the wind farms 302, the LODES systems 304, and / or the thermal power plants 902. As an example, the LODES systems 304 of the power plants 900 may have a duration of 24 hours to 500 hours. As a specific example, the C&I customers 702 load may be 100 MW peak, the LODES systems 304 may have a power rating of 14 MW and a duration of 150 hours, the cost of natural gas may be $6 / million British thermal units (MMBTU), and the renewable occupancy may be 58%. As another specific example, the C&I customer 702 load may be 100 MW peak, the LODES system 304 may have a power rating of 25 MW and a duration of 150 hours, the cost of natural gas may be $8 / million British thermal units (MMBTU), and the renewable occupancy may be 65%.

[0135] FIG. 11 illustrates an exemplary system in which one or more aspects of the various embodiments can be used as part of a bulk energy storage system. Although FIG. 11 is discussed in relation to an example LODES system 304, the duration of energy storage and / or power supply described with reference to FIG. 11 is provided by way of example only and is not intended to limit the scope of the present invention or claims. As a specific example, a bulk energy storage system incorporating one or more aspects of the various embodiments may be a LODES system 304. As an example, the LODES system 304 may include the batteries of the various embodiments described herein, the various electrodes described herein, and the like. The LODES system 304 can be used to enhance the nuclear power plant 1002 (or other inflexible power generating facilities such as thermal, biomass, and / or any other type of power plant with a ramp rate of less than 50% of rated power in one hour and a capacity factor of 80% or higher) to add flexibility to the combined output of the power plant 1000 comprised of the combined LODES system 304 and the nuclear power plant 1002. The nuclear power plant 1002 may operate at a high capacity factor and peak efficiency point, and the LODES system 304 may charge and discharge to effectively reshape the output of the nuclear power plant 1002 to match customer electricity consumption and / or market price of electricity. As an example, the LODES system 304 of the power plant 1000 may have a duration of 24 hours to 500 hours. In one specific example, the nuclear power plant 1002 may have a rated output of 1,000 MW, and the nuclear power plant 1002 may be forced to operate at minimum stable generation or even shut down for an extended period of time due to a drop in the market price of electricity. The LODES system 304 may avoid a facility shutdown and charge when the market price drops, and then the LODES system 304 may discharge when the market price rises to restore total output generation.

[0136] FIG. 12 illustrates an exemplary system in which one or more aspects of the various embodiments can be used as part of a bulk energy storage system. Although FIG. 12 is discussed in relation to examples of a LODES system 304 and an SDES system 1102, the duration of energy storage and / or power delivery described with reference to FIG. 12 is provided by way of example only and is not intended to limit the scope of the present invention or claims. As a specific example, a bulk energy storage system incorporating one or more aspects of the various embodiments may be a LODES system 304. As an example, the LODES system 304 may include the batteries of the various embodiments described herein, the various electrodes described herein, and the like. The LODES system 304 may operate in conjunction with an SDES system 1102. The LODES system 304 and the SDES system 1102 together may comprise a power plant 1100. As an example, the LODES system 304 and the SDES system 1102 can be co-optimized, such that the LODES system 304 can provide various services including long-term backup and / or bridging over multi-day variations (e.g., multi-day variations in market prices, renewable generation, electricity consumption, etc.). The SDES system 1102 can provide various services including quick backup services (e.g., voltage control, frequency regulation, etc.) and / or bridging over diurnal variations (e.g., diurnal variations in market prices, renewable generation, electricity consumption, etc.). The SDES system 1102 can have a duration of less than 10 hours and a round-trip efficiency of greater than 80%. The LODES system 304 can have a duration of 24 hours to 500 hours and a round-trip efficiency of greater than 40%. In one such example, the LODES system 304 can have a duration of 150 hours and can support customer electricity consumption for up to one week of renewable generation shortage. The LODES system 304 can also support customer electricity consumption during daytime generation shortage events, enhancing the capacity of the SDES system 1102 .Additionally, the SDES system 1102 can supply customers during daytime generation shortage events and provide power conditioning and quality services such as voltage control and frequency regulation.

[0137] Various examples are provided below to illustrate aspects of the various embodiments. Example 1: A battery electrode comprising an iron electrode body including an iron active material and a zinc sulfide additive, the zinc sulfide additive comprising crystalline cubic zinc sulfide. Example 2. The electrode of Example 1, wherein the crystalline cubic zinc sulfide has a high degree of crystallinity as measured by at least one indicator. Example 3. The electrode of Examples 1 or 2, wherein at least 75% by weight of the zinc sulfide additive is in the form of cubic zinc sulfide. Example 4. The electrode of Example 3, wherein at least 90% by weight of the zinc sulfide additive is in the form of cubic zinc sulfide. Example 5. The electrode of Example 4, wherein at least 99% by weight of the zinc sulfide additive is in the form of cubic zinc sulfide. Example 6. The electrode of Example 5, wherein 100% by weight of the zinc sulfide additive is in the form of cubic zinc sulfide. Example 7. The electrode of any one of Examples 1-6, wherein the crystalline cubic zinc sulfide is characterized by a non-zero X-ray diffraction (XRD) peak at 28.6±0.1 degrees with a full width at half maximum (FWHM) value of less than 0.4±0.1 degrees. Example 8. The electrode of any one of Examples 1-7, wherein the crystalline cubic zinc sulfide is characterized by a non-zero XRD peak at 47.6±0.1 degrees with a FWHM value of less than 0.5±0.1 degrees. Example 9. The electrode of any one of Examples 1-8, wherein the crystalline cubic zinc sulfide is characterized by a non-zero XRD peak at 56.4±0.1 degrees with a FWHM value of less than 0.6±0.1 degrees. Example 10. The electrode of any one of Examples 1-9, wherein the crystalline cubic zinc sulfide is present in the electrode as particles having a size between 0.1 microns and 500 microns. Example 11. The electrode of any one of Examples 1-10, wherein the crystalline cubic zinc sulfide is present in an amount of 0.01-20% by weight based on the weight of the iron active material. Example 12. An iron electrode battery comprising an iron electrode and a sulfide reservoir spaced from the iron electrode, the sulfide reservoir comprising crystalline cubic zinc sulfide. Example 13. The battery of Example 12, wherein the crystalline cubic zinc sulfide has a high degree of crystallinity as measured by at least one indicator. Example 14. The battery of Examples 12 or 13, wherein at least 75% by weight of the zinc sulfide additive is in the form of cubic zinc sulfide. Example 15. The battery of Example 14, wherein at least 90% by weight of the zinc sulfide additive is in the form of cubic zinc sulfide. Example 16. The battery of Example 15, wherein at least 99% by weight of the zinc sulfide additive is in the form of cubic zinc sulfide.Example 17. The battery of Example 16, wherein 100% by weight of the zinc sulfide additive is in the form of cubic zinc sulfide. Example 18. The battery of any one of Examples 1-17, wherein the crystalline cubic zinc sulfide is characterized by a non-zero X-ray diffraction (XRD) peak at 28.6±0.1 degrees with a full width at half maximum (FWHM) value of less than 0.4±0.1 degrees. Example 19. The battery of any one of Examples 1-18, wherein the crystalline cubic zinc sulfide is characterized by a non-zero XRD peak at 47.6±0.1 degrees with a FWHM value of less than 0.5±0.1 degrees. Example 20. The battery of any one of Examples 1-19, wherein the crystalline cubic zinc sulfide is characterized by a non-zero XRD peak at 56.4±0.1 degrees with a FWHM value of less than 0.6±0.1 degrees. Example 21. The battery of any one of Examples 1-20, wherein the crystalline cubic zinc sulfide is present in the electrode as particles having a size between 0.1 microns and 500 microns. Example 22. The battery of any one of Examples 1-21, wherein the crystalline cubic zinc sulfide is present in an amount between 0.01 and 20% by weight of the iron active material. Example 23. The battery of any one of Examples 1-22, wherein the battery is selected from the group consisting of an iron-air battery, a nickel-iron battery, and an iron-manganese dioxide battery. Example 24. The battery of any one of Examples 1-23, comprising an electrolyte having a sulfide concentration selected from the range of 0.01±20% mmol / L to 10±20% mmol / L during operation of the battery. Example 25. A battery electrode comprising an iron electrode body comprising an iron active material and a manganese sulfide additive, the manganese sulfide additive comprising crystalline cubic manganese sulfide. Example 26. The electrode of Example 25, wherein the crystalline cubic zinc sulfide has a high degree of crystallinity as measured by at least one index. Example 27. The electrode of Examples 25 or 26, wherein at least 75% by weight of the manganese sulfide additive is in the form of cubic manganese sulfide. Example 28. The electrode of Example 27, wherein at least 90% by weight of the manganese sulfide additive is in the form of cubic manganese sulfide. Example 29. The electrode of Example 28, wherein at least 99% by weight of the manganese sulfide additive is in the form of cubic manganese sulfide. Example 30. The electrode of Example 29, wherein 100% by weight of the manganese sulfide additive is in the form of cubic manganese sulfide. Example 31. The electrode of any one of Examples 25 to 30, wherein the crystalline cubic manganese sulfide is present in the electrode as particles having a size of 0.1 microns to 500 microns.Example 32. The electrode of any one of Examples 25-31, wherein the crystalline cubic manganese sulfide is present in an amount of 0.01-20% by weight of the iron active material. Example 33. An iron electrode battery comprising an iron electrode and a sulfide reservoir spaced from the iron electrode, the sulfide reservoir comprising crystalline cubic manganese sulfide. Example 34. The battery of Example 33, wherein the crystalline cubic zinc sulfide has a high degree of crystallinity as measured by at least one indicator. Example 35. The battery of Examples 33 or 34, wherein at least 75% by weight of the manganese sulfide additive is in the form of cubic manganese sulfide. Example 36. The battery of Example 35, wherein at least 90% by weight of the manganese sulfide additive is in the form of cubic manganese sulfide. Example 37. The battery of Example 36, wherein at least 99% by weight of the manganese sulfide additive is in the form of cubic manganese sulfide. Example 38. The battery of Example 37, wherein 100% by weight of the manganese sulfide additive is in the form of cubic manganese sulfide. Example 39. The battery of any one of Examples 33-38, wherein the crystalline cubic manganese sulfide is present in the electrode as crystallites having a size between 0.1 microns and 500 microns. Example 40. The battery of any one of Examples 33-39, wherein the crystalline cubic manganese sulfide is present in an amount between 0.01 and 20% by weight of the iron active material. Example 41. The battery of any one of Examples 1-40, wherein the battery is a member of the group consisting of an iron-air battery, a nickel-iron battery, and an iron-manganese dioxide battery. Example 42. The battery of any one of Examples 1-41, comprising an electrolyte having a sulfide concentration selected from the range of 0.01±20% mmol / L to 10±20% mmol / L. Example 43. The battery of any one of Examples 1-42, comprising a positive electrode, a negative electrode, and at least one electrolyte, the negative electrode comprising the iron electrode of any one of Examples 1-42. Example 44. A method of making the battery of any one of Examples 1-43, comprising making an iron electrode body comprising an iron active material and a manganese sulfide additive and / or a zinc sulfide additive. Example 45. A method of making the electrode of any one of Examples 1-44, comprising making an iron electrode body comprising an iron active material and a manganese sulfide additive and / or a zinc sulfide additive. Example 46. The method of Example 44 or 45, comprising combining a manganese sulfide additive and / or a zinc sulfide additive with an iron active material.Example 47. A method of operating the battery of any one of Examples 1 to 46, comprising: charging and / or discharging the battery, the battery comprising an anode, a cathode, and an electrolyte, the anode comprising the iron electrode of any one of Examples 1 to 46; and maintaining a sulfide concentration selected from the range of 0.01±20% mmol / L to 10±20% mmol / L during the charging and / or discharging steps. Example 48. The battery of any one of Examples 1 to 47, wherein prior to and / or during operation of the battery, the iron electrode comprises less than 1% by weight of any combination of amorphous ZnS, non-structured cubic ZnS, crystalline hexagonal ZnS, amorphous MnS, non-structured cubic MnS, and crystalline hexagonal MnS. Example 49. The electrode of any one of Examples 1-48, comprising less than 1% by weight of any combination of amorphous ZnS, unstructured cubic ZnS, crystalline hexagonal ZnS, amorphous MnS, unstructured cubic MnS, and crystalline hexagonal MnS.

[0138] Example A. A battery electrode comprising an iron electrode body comprising an iron active material and a zinc sulfide additive, the zinc sulfide additive comprising crystalline cubic zinc sulfide. Example B. The electrode of Example A, wherein the crystalline cubic zinc sulfide has a high degree of crystallinity as measured by at least one indicator. Example C1. The electrode of Example A or B, wherein at least 50% by weight of the zinc sulfide additive is in the form of cubic zinc sulfide. Example C2. The electrode of Example A or B, wherein at least 75% by weight of the zinc sulfide additive is in the form of cubic zinc sulfide. Example C3. The electrode of Example C2, wherein at least 90% by weight of the zinc sulfide additive is in the form of cubic zinc sulfide. Example D. The electrode of Example C2, wherein at least 95% by weight of the zinc sulfide additive is in the form of cubic zinc sulfide. Example E. The electrode of Example C3, wherein at least 99% by weight of the zinc sulfide additive is in the form of cubic zinc sulfide. Example F. The electrode of Example E, wherein 100% by weight of the zinc sulfide additive is in the form of cubic zinc sulfide.Example G1. The electrode of any one of Examples 1-F, wherein the crystalline cubic zinc sulfide is characterized by a non-zero X-ray diffraction (XRD) peak at 28.6 degrees with a full width at half maximum (FWHM) value of less than 0.4±0.1 degrees for cubic ZnS with Miller indices (111) as measured by the Rietveld technique.Example G2. The electrode of any one of Examples 1-G1, wherein the crystalline cubic zinc sulfide is characterized by a non-zero X-ray diffraction (XRD) peak at 28.6 degrees with a full width at half maximum (FWHM) value of less than 0.6±0.1 degrees for cubic ZnS with Miller indices (111) as measured by the Rietveld technique. Example G3. The electrode of any one of Examples 1-G2, wherein the crystalline cubic zinc sulfide is characterized by a non-zero X-ray diffraction (XRD) peak having a full width at half maximum (FWHM) value of less than 0.45±0.1 degrees at 28.6 degrees for cubic ZnS with Miller indices (111) as measured by the Rietveld technique. Example G4. The electrode of any one of Examples 1-G3, wherein the crystalline cubic zinc sulfide is characterized by a non-zero X-ray diffraction (XRD) peak having a full width at half maximum (FWHM) value of less than 0.3±0.1 degrees at 28.6 degrees for cubic ZnS with Miller indices (111) as measured by the Rietveld technique.Example H1. The electrode of any one of Examples 1-G4, wherein the crystalline cubic zinc sulfide is characterized by a non-zero XRD peak at 47.6 degrees with a FWHM value of less than 0.5±0.1 degrees for cubic ZnS with Miller index (220) as measured by the Rietveld technique. Example H2. The electrode of any one of Examples 1-H1, wherein the crystalline cubic zinc sulfide is characterized by a non-zero XRD peak at 47.6 degrees with a FWHM value of less than 0.45±0.1 degrees for cubic ZnS with Miller index (220) as measured by the Rietveld technique. Example H3. The electrode of any one of Examples 1-H2, wherein the crystalline cubic zinc sulfide is characterized by a non-zero XRD peak at 47.6 degrees with a FWHM value of less than 0.3±0.1 degrees for cubic ZnS with Miller index (220) as measured by the Rietveld technique. Example H4. The electrode of any one of Examples 1-H3, wherein the crystalline cubic zinc sulfide is characterized by a non-zero XRD peak at 47.6 degrees with a FWHM value of less than 0.6±0.1 degrees for cubic ZnS with Miller index (220) as measured by the Rietveld technique. Example H5. The electrode of any one of Examples 1-H4, wherein the crystalline cubic zinc sulfide is characterized by a non-zero XRD peak at 47.6 degrees with a FWHM value of less than 0.35±0.1 degrees for cubic ZnS with Miller index (220) as measured by the Rietveld technique. Example H6. The electrode of any one of Examples 1-H5, wherein the crystalline cubic zinc sulfide is characterized by a non-zero XRD peak at 47.6 degrees with a FWHM value of less than 0.2±0.1 degrees for cubic ZnS with Miller index (220) as measured by the Rietveld technique. Example I1. The electrode of any one of Examples 1-H6, wherein the crystalline cubic zinc sulfide is characterized by a non-zero XRD peak at 56.4 degrees with a FWHM value of less than 0.6±0.1 degrees for cubic ZnS with Miller indices (311) as measured by the Rietveld technique. Example I2. The electrode of any one of Examples 1-I1, wherein the crystalline cubic zinc sulfide is characterized by a non-zero XRD peak at 56.4 degrees with a FWHM value of less than 0.45±0.1 degrees for cubic ZnS with Miller indices (311) as measured by the Rietveld technique.Example I3. The electrode of any one of Examples 1-I2, wherein the crystalline cubic zinc sulfide is characterized by a non-zero XRD peak at 56.4 degrees with a FWHM value of less than 0.35±0.1 degrees for cubic ZnS with Miller index (311) as measured by the Rietveld technique. Example J1. The electrode of any one of Examples 1-I3, wherein the crystalline cubic zinc sulfide is characterized by a non-zero XRD peak at 33.1 degrees with a FWHM value of less than 0.6±0.1 degrees for cubic ZnS with Miller index (200) as measured by the Rietveld technique. Example J2. The electrode of any one of Examples 1-J1, wherein the crystalline cubic zinc sulfide is characterized by a non-zero XRD peak at 33.1 degrees with a FWHM value of less than 0.45±0.1 degrees for cubic ZnS with Miller index (200) as measured by the Rietveld technique. Example J3. The electrode of any one of Examples 1-J2, wherein the crystalline cubic zinc sulfide is characterized by a non-zero XRD peak at 33.1 degrees with a FWHM value of less than 0.4±0.1 degrees for cubic ZnS with Miller index (200) as measured by the Rietveld technique. Example J4. The electrode of any one of Examples 1-J3, wherein the crystalline cubic zinc sulfide is characterized by a non-zero XRD peak at 33.1 degrees with a FWHM value of less than 0.3±0.1 degrees for cubic ZnS with Miller index (200) as measured by the Rietveld technique. Example J5. The electrode of any one of Examples 1-J4, wherein the crystalline cubic zinc sulfide is characterized by a non-zero XRD peak at 33.1 degrees with a FWHM value of less than 0.2±0.1 degrees for cubic ZnS with Miller index (200) as measured by the Rietveld technique. Example K. The electrode of any one of Examples 1-J5, wherein the crystalline cubic zinc sulfide is present in the electrode as particles having a size between 0.1 microns and 500 microns. Example L. The electrode of any one of Examples 1-K, wherein the crystalline cubic zinc sulfide is present in an amount between 0.01 and 20% by weight based on the weight of the iron active material. Example M. An iron electrode battery comprising an iron electrode and a sulfide reservoir spaced from the iron electrode, the sulfide reservoir comprising crystalline cubic zinc sulfide. Example N. The battery of Example M, wherein the crystalline cubic zinc sulfide has a high degree of crystallinity as measured by at least one indicator. Example O. The battery of Example M or N, wherein at least 50% by weight of the zinc sulfide additive is in the form of cubic zinc sulfide.Example P. The battery of Example O, wherein at least 75% by weight of the zinc sulfide additive is in the form of cubic zinc sulfide. Example Q. The battery of Example P, wherein at least 90% by weight of the zinc sulfide additive is in the form of cubic zinc sulfide. Example R1. The battery of Example Q, wherein 95% by weight of the zinc sulfide additive is in the form of cubic zinc sulfide. Example R2. The battery of Example Q, wherein 99% by weight of the zinc sulfide additive is in the form of cubic zinc sulfide. Example R3. The battery of Example Q, wherein 100% by weight of the zinc sulfide additive is in the form of cubic zinc sulfide. Example S. The battery of any one of Examples 1-R3, wherein the crystalline cubic zinc sulfide is characterized by a non-zero X-ray diffraction (XRD) peak at 28.6±0.1 degrees having a full width at half maximum (FWHM) value of less than 0.4±0.1 degrees. Example T. The battery of any one of Examples 1-S, wherein the crystalline cubic zinc sulfide is characterized by a non-zero XRD peak at 47.6±0.1 degrees with a FWHM value of less than 0.5±0.1 degrees. Example U. The battery of any one of Examples 1-T, wherein the crystalline cubic zinc sulfide is characterized by a non-zero XRD peak at 56.4±0.1 degrees with a FWHM value of less than 0.6±0.1 degrees. Example K. The electrode of any one of Examples 1-U, wherein the crystalline cubic zinc sulfide is present in the electrode as particles with a size between 0.1 microns and 500 microns. Example W. The battery of any one of Examples 1-V, wherein the crystalline cubic zinc sulfide is present in an amount between 0.01 and 20% by weight of the iron active material. Example X. The battery of any one of Examples 1-W, wherein the battery is selected from the group consisting of an iron-air battery, a nickel-iron battery, and an iron-manganese dioxide battery. Example Y. The battery of any one of Examples 1-X, comprising an electrolyte having a sulfide concentration selected from the range of 0.01±20% mmol / L to 10±20% mmol / L during operation of the battery. Example Z. A battery electrode comprising an iron electrode body comprising an iron active material and a manganese sulfide additive, the manganese sulfide additive comprising crystalline cubic manganese sulfide. Example AA. The electrode of Example Z, wherein the crystalline cubic manganese sulfide has a high degree of crystallinity as measured by at least one indicator. Example AB. The electrode of Example Z or AA, wherein at least 50% by weight of the manganese sulfide additive is in the form of cubic manganese sulfide. Example AC. The electrode of Example AB, wherein at least 75% by weight of the manganese sulfide additive is in the form of cubic manganese sulfide.Example AD. The electrode of Example AC, wherein at least 90% by weight of the manganese sulfide additive is in the form of cubic manganese sulfide. Example AE1. The electrode of Example AD, wherein 95% by weight of the manganese sulfide additive is in the form of cubic manganese sulfide. Example AE2. The electrode of Example AD, wherein 99% by weight of the manganese sulfide additive is in the form of cubic manganese sulfide. Example AE3. The electrode of Example AD, wherein 100% by weight of the manganese sulfide additive is in the form of cubic manganese sulfide. Example AF. The electrode of any one of Examples Z-AE3, wherein the crystalline cubic manganese sulfide is present in the electrode as particles having a size between 0.1 microns and 500 microns. Example AG. The electrode of any one of Examples Z-AF, wherein the crystalline cubic manganese sulfide is present in an amount between 0.01 and 20% by weight of the iron active material. Example AH. An iron electrode battery comprising an iron electrode and a sulfide reservoir spaced from the iron electrode, the sulfide reservoir comprising crystalline cubic manganese sulfide. Example AI. The battery of Example AH, wherein the crystalline cubic manganese sulfide has a high degree of crystallinity as measured by at least one indicator. Example AJ. The battery of Example AH or AI, wherein at least 50% by weight of the manganese sulfide additive is in the form of cubic manganese sulfide. Example AJ. The battery of Example AJ, wherein at least 75% by weight of the manganese sulfide additive is in the form of cubic manganese sulfide. Example AK. The battery of Example AJ, wherein at least 90% by weight of the manganese sulfide additive is in the form of cubic manganese sulfide. Example AL1. The battery of Example AK, wherein 95% by weight of the manganese sulfide additive is in the form of cubic manganese sulfide. Example AL2. The battery of Example AK, wherein 99% by weight of the manganese sulfide additive is in the form of cubic manganese sulfide. Example AL3. The battery of Example AK, wherein 100% by weight of the manganese sulfide additive is in the form of cubic manganese sulfide. Example AM. The battery of any one of Examples AH-AL3, wherein the crystalline cubic manganese sulfide is present in the electrode as crystallites having a size between 0.1 microns and 500 microns. Example AN. The battery of any one of Examples AH-AM, wherein the crystalline cubic manganese sulfide is present in an amount between 0.01 and 20% by weight of the iron active material. Example AO. The battery of any one of Examples 1-AN, wherein the battery is a member of the group consisting of an iron-air battery, a nickel-iron battery, and an iron-manganese dioxide battery. Example AP. The battery of any one of Examples 1-AO, comprising an electrolyte having a sulfide concentration selected from the range of 0.01±20% mmol / L to 10±20% mmol / L. Example AQ. The battery of any one of Examples 1-AP, comprising a positive electrode, a negative electrode, and at least one electrolyte, wherein the negative electrode comprises the iron electrode of any one of Examples 1-AP.Example AR. The battery of any one of Examples 1-AQ, comprising a positive electrode, a negative electrode, and at least one electrolyte, the negative electrode comprising antimony sulfide, bismuth sulfide, cadmium sulfide, cerium sulfide, cobalt sulfide, copper sulfide, copper disulfide, indium sulfide, iron sulfide, iron disulfide, lead sulfide, manganese disulfide, mercury sulfide, molybdenum disulfide, nickel sulfide, silver disulfide, and tin sulfide. Example AS. A method of making the battery of any one of Examples 1-AR, comprising fabricating an iron electrode body comprising an iron active material and at least one of a manganese sulfide additive and a zinc sulfide additive. Example AT. A method of making the electrode of any one of Examples 1-AS, comprising fabricating an iron electrode body comprising an iron active material and at least one of a manganese sulfide additive and a zinc sulfide additive. Example AU. The method of Example AS or AT, comprising combining a manganese sulfide additive and / or a zinc sulfide additive with an iron active material.Example AV. A method of operating the battery of any one of Examples 1-AU, comprising: charging and / or discharging the battery, the battery comprising an anode, a cathode, and an electrolyte, the anode comprising the iron electrode of any one of Examples 1-AU; and maintaining a sulfide concentration selected from the range of 0.01±20% mmol / L to 10±20% mmol / L during the charging and / or discharging steps.Example AW. The battery of any one of Examples 1-AV, wherein prior to and / or during operation of the battery, the iron electrode comprises less than 1% by weight of any combination of amorphous ZnS, non-structured cubic ZnS, crystalline hexagonal ZnS, amorphous MnS, non-structured cubic MnS, and crystalline hexagonal MnS. Example AX. The electrode of any one of Examples 1-AW comprising less than 1% by weight of any combination of amorphous ZnS, unstructured cubic ZnS, crystalline hexagonal ZnS, amorphous MnS, unstructured cubic MnS, and crystalline hexagonal MnS. Example AY. A bulk energy storage system comprising one or more electrodes and / or one or more batteries of any of Examples A-AX. Example AZ. A long-term energy storage system configured to hold a charge for at least 24 hours, the system comprising one or more electrodes and / or one or more battery systems of any of Examples A-AX.

[0139] Any of the aspects and embodiments disclosed herein may be combined with any of the aspects and embodiments disclosed in the above-referenced Pham Publication '702.

[0140] Although the present invention has been disclosed with respect to certain preferred embodiments and examples, those skilled in the art will appreciate that the present invention extends beyond the specifically disclosed embodiments to other alternative embodiments and / or uses of the invention, as well as obvious modifications and equivalents thereof. Various modifications to the above-described embodiments will be readily apparent to those skilled in the art, and the basic principles defined herein may be applied to other embodiments without departing from the spirit or scope of the invention. Thus, it is intended that the scope of the invention disclosed herein is not limited to the above-described specific disclosed embodiments, but rather be determined solely by a fair reading of the following claims.

[0141] The term "substantially" refers to a property, condition, or value that is within 20%, 10%, 5%, 1%, optionally within 0.1%, or equivalent to a referenced property, condition, or value. The terms "substantially equal," "substantially equivalent," or "unaltered," when used with a reference value describing a property or condition, refer to a value that is within 20%, 10%, optionally within 5%, optionally within 1%, optionally within 0.1%, or optionally equivalent to the given reference value. For example, a diameter is substantially equal to 100 nm (or "is substantially 100 nm") if the diameter value is within 20%, optionally within 10%, optionally within 5%, optionally within 1%, optionally within 0.1%, or optionally equivalent to 100 nm. The term "substantially larger", when used with a reference value describing a property or condition, refers to a value that is at least 1%, optionally at least 5%, optionally at least 10%, or optionally at least 20% larger than the given reference value. The term "substantially smaller", when used with a reference value describing a property or condition, refers to a value that is at least 1%, optionally at least 5%, optionally at least 10%, or optionally at least 20% smaller than the given reference value. As used herein, the terms "about" and "substantially" are interchangeable and have the same meaning. For example, a particle having a size of about 1 μm is understood to have a size that is within 20%, optionally within 10%, optionally within 5%, optionally within 1%, optionally within 0.1%, or optionally equal to 1 μm.

[0142] In particular, materials and manufacturing techniques may be used that are within the level of ordinary skill in the art. Moreover, reference to a singular item includes the possibility of a plurality of the same items. More specifically, as used herein and in the appended claims, the singular forms "a," "and," "above," and "the" include plural references unless the context clearly dictates otherwise. As used herein, unless expressly stated otherwise, the term "or" includes all presented alternatives and has essentially the same meaning as the phrase "and / or." It should be noted that the claims may be drafted to exclude any optional element. Thus, this statement is intended to serve as a predicate for the use of exclusive terms such as "solely," "only," and the like, or the use of "negative" limitations in connection with the recitation of claim elements. Unless otherwise defined herein, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains.

[0143] The term "and / or" as used herein and in the claims refers to only a single element or any combination of elements from the list in which the term "and / or" is stated. In other words, a list of two or more elements with the term "and / or" is intended to cover embodiments having any of the individual elements alone or any combination of the listed elements. For example, the phrase "element A and / or element B" is intended to cover embodiments having only element A, only element B, or both element A and element B together. For example, the phrase "element A, element B, and / or element C" is intended to cover embodiments having only element A, only element B, only element C, or element A and element B together, element A and element C together, element B and element C together, or element A, element B, and element C together.

[0144] The term "±" refers to an inclusive range of values, such as "X±Y," where X and Y are each independent numbers and refer to an inclusive range of values ​​selected from the range XY to X+Y.

[0145] As used herein, unless otherwise stated, recitation of ranges of values ​​herein is merely intended to serve as a shorthand method of referring individually to each separate value falling within the range. Unless otherwise stated herein, each individual value within a range is incorporated herein as if it were individually recited herein.

Claims

1. A battery electrode, 1. A battery electrode comprising: an iron electrode body comprising an iron active material and a zinc sulfide additive, the zinc sulfide additive comprising crystalline cubic zinc sulfide.

2. 10. The battery electrode of claim 1, wherein the crystalline cubic zinc sulfide has a high degree of crystallinity as measured by at least one index.

3. 10. The battery electrode of claim 1, wherein at least 50% by weight of the zinc sulfide additive is in the form of cubic zinc sulfide.

4. 4. The battery electrode of claim 3, wherein at least 75% by weight of the zinc sulfide additive is in the form of cubic zinc sulfide.

5. 5. The battery electrode of claim 4, wherein at least 90% by weight of the zinc sulfide additive is in the form of cubic zinc sulfide.

6. 6. The battery electrode of claim 5, wherein 95% by weight of the zinc sulfide additive is in the form of cubic zinc sulfide.

7. 2. The battery electrode of claim 1, wherein the crystalline cubic zinc sulfide is characterized by a non-zero X-ray diffraction (XRD) peak at 28.6 degrees with Miller indices (111) for cubic ZnS having a full width at half maximum (FWHM) value of less than 0.6±0.1 degrees as measured by the Rietveld technique.

8. 2. The battery electrode of claim 1, wherein the crystalline cubic zinc sulfide is characterized by a non-zero XRD peak at 47.6 degrees with a FWHM value of less than 0.5±0.1 degrees for cubic ZnS with Miller index (220) as measured by the Rietveld technique.

9. 2. The battery electrode of claim 1, wherein the crystalline cubic zinc sulfide is characterized by a non-zero XRD peak at 56.4 degrees with Miller indices (311) for cubic ZnS having a FWHM value of less than 0.6±0.1 degrees as measured by the Rietveld technique.

10. 2. The battery electrode of claim 1, wherein the crystalline cubic zinc sulfide is characterized by a non-zero XRD peak at 33.1 degrees with a FWHM value of less than 0.6±0.1 degrees for cubic ZnS with Miller indices (200) as measured by the Rietveld technique.

11. 2. The battery electrode of claim 1, wherein the crystalline cubic zinc sulfide is in particles ranging in size from 0.1 microns to 500 microns.

12. 2. The battery electrode of claim 1, wherein the crystalline cubic zinc sulfide is present in an amount of 0.01% to 20% by weight based on the weight of the iron active material.